Conductive particles, conductive materials, and connection structures

By using conductive particles arranged on the surface of the base particle with a solder portion that can be diffused or melted at 400°C or below, the problem of solder particles is solved, and a high-reliability electrical connection is achieved.

CN113950778BActive Publication Date: 2025-04-04SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080042463.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-13
Filing Date
2020-06-12
Publication Date
2025-04-04
Estimated Expiration
2040-06-12

AI Technical Summary

Technical Problem

The prior art is difficult to deal with narrow pitch in the connection between substrates and electronic components, and solder particles in the solder paste tend to condense, resulting in aggregation problem between conductive particles.

Method used

Conductive particles having solder portions are used, and metal diffusion or melt deformation occurs at 400°C or less, and the area of ​​the solder portion in the total surface area of ​​the substrate particles is less than 99% to suppress aggregation between the conductive particles.

Benefits of technology

The aggregation between conductive particles is effectively suppressed, the conduction reliability between electrodes is improved, and the need to increase the thickness of the conductive portion to prevent aggregation is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113950778B_ABST
    Figure CN113950778B_ABST
Patent Text Reader

Abstract

The present invention provides conductive particles that can effectively suppress aggregation of conductive particles. The conductive particles of the present invention include: substrate particles and a conductive portion disposed on the surface of the substrate particles, the conductive portion containing a component that can cause metal diffusion at 400°C or below, or the conductive portion can be melt-deformed at 400°C or below, the conductive portion having a solder portion, and the area of ​​the portion having the solder portion is 99% or less of the total surface area of ​​the substrate particles (100%).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to conductive particles having a conductive portion disposed on the surface of substrate particles. In addition, the present invention relates to a conductive material and a bonded structure using the conductive particles. Background Art

[0002] Electronic components in which a connector (first component) and a printed circuit board (second component) are electrically connected via pins are well known. In the electronic component, the pins are inserted into through holes formed on the printed circuit board, or are directly arranged on electrode portions on a wiring board, and are connected to the printed circuit board by soldering.

[0003] Patent document 1 below discloses an electronic component connection structure in which a plurality of pins (20) connected to a first component (10) at one end are arranged using an arrangement component (50) and connected to a second component (30) at the other end. In the electronic component connection structure, after the arrangement component (50) arranges the pins (20) at the outer periphery in an axial direction (A), it is rotated with reference to the axial direction (A) and detached from the pins (20), and removed from the pins (20).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2000-294997 Summary of the invention

[0007] Technical problem solved by the invention

[0008] In recent years, electronic devices have been thinned and miniaturized. Therefore, in the connection between substrates and electronic components, it is difficult to cope with the narrow pitch in the connection using pins in the past. Therefore, solder paste is sometimes used in the electrical connection between substrates and electronic components.

[0009] However, in the case of conventional solder paste, solder particles may aggregate with each other.

[0010] An object of the present invention is to provide conductive particles capable of effectively suppressing aggregation of conductive particles. Another object of the present invention is to provide a conductive material and a bonded structure using the conductive particles.

[0011] Technical means of solving problems

[0012] According to a broad scheme of the present invention, there is provided a conductive particle comprising: a substrate particle and a conductive portion arranged on the surface of the substrate particle, wherein the conductive portion contains a component that can undergo metal diffusion at a temperature below 400°C, or the conductive portion can undergo melting deformation at a temperature below 400°C, and the conductive portion has a solder portion, and the area of ​​the portion having the solder portion is 99% or less in 100% of the total surface area of ​​the substrate particle.

[0013] In a specific aspect of the conductive particle according to the present invention, the solder portion is a solder particle.

[0014] In a specific embodiment of the conductive particle of the present invention, the material of the solder particles contains a tin-containing alloy, or the material of the solder particles is pure tin, or the material of the solder particles contains tin in a state different from the tin-containing alloy and in a state different from pure tin.

[0015] In a specific embodiment of the conductive particles of the present invention, the material of the solder particles is pure tin.

[0016] In a specific aspect of the conductive particles of the present invention, the height of the solder particles is 10 nm or more and 10 μm or less.

[0017] In a specific embodiment of the conductive particles of the present invention, the aspect ratio of the solder particles is 0.05 to 5.

[0018] In a specific aspect of the conductive particle of the present invention, the conductive particle has a metal colloid precipitate or a metal film on the outer surface of the solder particle.

[0019] In a specific embodiment of the conductive particle of the present invention, the area of ​​the portion having the metal colloid precipitate or the metal film is 5% to 100% of the total surface area (100%) of the solder particle.

[0020] In a specific embodiment of the conductive particle of the present invention, the metal species of the metal colloid precipitate or the metal species of the metal film is nickel, cobalt, lead, gold, zinc, palladium, copper, silver, bismuth or indium.

[0021] In a specific embodiment of the conductive particles of the present invention, the particle diameter is 0.5 μm or more and 500 μm or less.

[0022] According to a broad aspect of the present invention, there is provided a conductive material comprising conductive particles and a binder, wherein the conductive particles are the above-described conductive particles.

[0023] According to a broad scheme of the present invention, there is provided a connection structure comprising: a first connection object component having a first electrode on a surface, a second connection object component having a second electrode on a surface, and a connection portion connecting the first connection object component and the second connection object component, the connection portion being formed by conductive particles, or by a conductive material comprising the conductive particles and an adhesive, the conductive particles being the above-mentioned conductive particles, and the first electrode and the second electrode being electrically connected via the conductive particles.

[0024] Effects of the Invention

[0025] The conductive particles of the present invention include substrate particles and a conductive portion arranged on the surface of the substrate particles. In the conductive particles of the present invention, the conductive portion includes a component that can cause metal diffusion at a temperature below 400°C, or the conductive portion can be melt-deformed at a temperature below 400°C. In the conductive particles of the present invention, the conductive portion has a solder portion. In the conductive particles of the present invention, the area of ​​the portion having the solder portion is 99% or less out of 100% of the total surface area of ​​the substrate particles. Since the conductive particles of the present invention have the above-mentioned structure, it is possible to effectively suppress the aggregation of the conductive particles with each other. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] [ Figure 1 ] Figure 1 This is a cross-sectional view showing the conductive particles according to the first embodiment of the present invention.

[0027] [ Figure 2 ] Figure 2 It is a cross-sectional view showing the conductive particles according to the second embodiment of the present invention.

[0028] [ Figure 3 ] Figure 3 It is a cross-sectional view which shows the electroconductive particle which concerns on 3rd Embodiment of this invention.

[0029] [ Figure 4 ] Figure 4 It is a cross-sectional view showing the conductive particles according to the fourth embodiment of the present invention.

[0030] [ Figure 5 ] Figure 5 It is a cross-sectional view showing the conductive particle according to the fifth embodiment of the present invention.

[0031] [ Figure 6 ] Figure 6 It is a cross-sectional view showing the conductive particles according to the sixth embodiment of the present invention.

[0032] [ Figure 7 ] Figure 7 This is a cross-sectional view showing conductive particles according to a seventh embodiment of the present invention.

[0033] [ Figure 8 ] Figure 8 It is a cross-sectional view showing the conductive particles according to the eighth embodiment of the present invention.

[0034] [ Fig. 9 ] Fig. 9 It is a front cross-sectional view schematically showing a connection structure using conductive particles according to a third embodiment of the present invention.

[0035] [ Fig.10 ] Fig.10 is enlarged and schematically represented Fig. 9 2 is a front cross-sectional view of a connection portion between conductive particles and an electrode in a connection structure shown in FIG.

[0036] Specific embodiments of the present invention

[0037] Hereinafter, the details of the present invention will be described.

[0038] (Conductive particles)

[0039] The conductive particles of the present invention include: substrate particles and a conductive portion arranged on the surface of the substrate particles. In the conductive particles of the present invention, the conductive portion contains a component that can cause metal diffusion at 400°C or less, or the conductive portion can be melt-deformed at 400°C or less. In the conductive particles of the present invention, the conductive portion may contain a component that can cause metal diffusion at 400°C or less, or the conductive portion can be melt-deformed at 400°C or less. In the conductive particles of the present invention, the conductive portion may contain a component that can cause metal diffusion at 400°C or less, and the conductive portion can be melt-deformed at 400°C or less. In the conductive particles of the present invention, the conductive portion has a solder portion. In the conductive particles of the present invention, the area of ​​the portion having the solder portion is 99% or less in 100% of the total surface area of ​​the substrate particles.

[0040] It should be noted that metal diffusion in the present invention refers to the diffusion of metal atoms into the conductive portion and the connecting portion due to heat, pressure, deformation, and the like.

[0041] In addition, the melt deformation in the present invention refers to a state in which a part or all of its components are melted and thus it becomes easy to deform due to external pressure.

[0042] Since the conductive particles of the present invention have the above-mentioned structure, aggregation of the conductive particles can be effectively suppressed.

[0043] In recent years, electronic devices have been thinned and miniaturized. Therefore, in the connection between substrates and electronic components, it is difficult to cope with the narrow pitch in the connection using pins in the past. Therefore, solder paste is sometimes used in the electrical connection between substrates and electronic components.

[0044] However, in the case of conventional solder paste, solder particles may aggregate with each other.

[0045] The inventors have found that by using specific conductive particles, the aggregation of conductive particles can be suppressed. In the present invention, the conductive portion contains a component that can cause metal diffusion at 400°C or less, or the conductive portion can be melted and deformed at 400°C or less. In the conductive particles of the present invention, the conductive portion has a solder portion. The solder portion is preferably a solder particle. In the conductive particles of the present invention, the conductive portion can form a metal bond between the bonding portions of electrodes, etc., and the solder portion (solder particles) can form a metal bond between the bonding portions of electrodes, etc. Therefore, compared with the previous physical contact, excellent conduction characteristics can be obtained dramatically. In addition, in the conductive particles of the present invention, the solder portion (solder particles) can form a metal bond between the bonding portions of electrodes, etc., so when bonding, it is not necessary to melt the conductive portion as a whole. As a result, in the present invention, even when the thickness of the conductive portion is thin, the conduction reliability between the electrodes can be improved. In addition, in the present invention, it is not necessary to increase the thickness of the conductive portion, so the aggregation of conductive particles can be effectively suppressed.

[0046] In the present invention, use of specific conductive particles greatly contributes to obtaining the above-mentioned effects.

[0047] The temperature at which the components of the conductive part can undergo metal diffusion and the melting deformation temperature of the conductive part can be achieved by selecting the material of the conductive part. For example, by using solder or a solder alloy as the material of the conductive part to form a solder part, the temperature at which the components of the conductive part can undergo metal diffusion and the melting deformation temperature of the conductive part can be easily set to 400°C or less. In the conductive particles, the conductive part has a solder part. The conductive part can be a solder part.

[0048] The metal diffusion state of the conductive portion was evaluated in the following manner.

[0049] A conductive paste containing 10% by weight of conductive particles was prepared.

[0050] A transparent glass substrate having a copper electrode on its upper surface is prepared, and a semiconductor chip having a gold electrode on its lower surface is prepared.

[0051] A conductive paste was applied on the transparent glass substrate to form a conductive paste layer. Next, the semiconductor chip was stacked on the conductive paste layer so that the electrodes were opposite to each other. Then, while adjusting the temperature of the head so that the temperature of the conductive paste layer was 250° C., a pressurizing heating head was placed on the upper surface of the semiconductor chip, a pressure of 0.5 MPa was applied, and the conductive paste layer was cured at 250° C. to obtain a connection structure.

[0052] Mechanical grinding is performed in a manner passing through the vicinity of the center of the connection structure, and the cross section of the conductive particles is cut out using an ion milling device. It should be noted that in order to facilitate mechanical grinding of the connection structure, the connection structure can be buried in a resin and the connection structure buried in the resin can be mechanically ground.

[0053] Next, using a transmission electron microscope FE-TEM, line analysis or element mapping was performed on the contact portions between the conductive particles and the copper electrode and the gold electrode using an energy dispersive X-ray analyzer (EDX) to observe the diffusion state of the metal.

[0054] By observing the diffusion state of the metal, it was confirmed that the metal was diffused into the copper electrode and the gold electrode from the periphery of the conductive particles.

[0055] Furthermore, by mapping the diffusion state of the metal, the contact ratio between the outer periphery of the conductive particle and the copper electrode and the gold electrode can be calculated, thereby enabling quantitative determination.

[0056] The melt deformation temperature of the conductive portion was evaluated in the following manner.

[0057] The melt deformation temperature of the conductive part can be measured using a differential scanning calorimeter ("DSC-6300" manufactured by Yamato Scientific Co., Ltd.) The measurement is performed using 15 g of conductive particles under the conditions of a temperature increase range of 30°C to 500°C, a temperature increase rate of 5°C / min., and a nitrogen injection amount of 5 ml / min.

[0058] Next, confirm that the conductive portion melts at the melting temperature obtained by the measurement. 1g of conductive particles is put into a container and placed in an electric furnace. The electric furnace is set to the same temperature as the melting temperature obtained by the measurement and heated for 10 minutes under a nitrogen atmosphere. Then, the heated conductive particles are taken out of the electric furnace and the molten state (or solidified state after melting) of the conductive portion is confirmed using a scanning electron microscope. It should be noted that the conductive portion can be melted and deformed by melting a portion of the conductive portion such as the solder portion (solder particles).

[0059] In the conductive particles of the present invention, the area of ​​the portion having the solder portion (the coverage of the solder portion) is 99% or less out of 100% of the total surface area of ​​the substrate particles. The area of ​​the portion having the solder portion (the coverage of the solder portion) is preferably 95% or less out of 100% of the total surface area of ​​the substrate particles, more preferably 90% or less, further preferably 85% or less, and particularly preferably 70% or less. The area of ​​the portion having the solder portion (the coverage of the solder portion) is preferably 5% or more out of 100% of the total surface area of ​​the substrate particles, more preferably 30% or more, and further preferably 60% or more. When the coverage (the coverage of the solder portion) is above the lower limit and below the upper limit, the aggregation of the conductive particles can be further effectively suppressed. When the coverage (the coverage of the solder portion) is above the lower limit, it is possible to further easily form a metal bond between the bonding portion of the solder portion and the electrode, etc.

[0060] The area of ​​the portion having the solder portion out of 100% of the total surface area of ​​the substrate particles (coverage of the solder portion) can be calculated by performing SEM-EDX analysis on the cross section of the conductive particles and element mapping and image analysis.

[0061] The particle size of the conductive particles is preferably 0.5 μm or more, more preferably 1 μm or more, preferably 500 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle size of the conductive particles is above the lower limit and below the upper limit, the contact area between the conductive particles and the electrode can be sufficiently increased, and when the conductive portion is formed, it is difficult to form agglomerated conductive particles, and the conductive portion is difficult to be peeled off from the surface of the substrate particles.

[0062] The particle size of the conductive particles is preferably an average particle size, preferably a number average particle size. The particle size of the conductive particles can be, for example, calculated by observing any 50 conductive particles using an electron microscope or an optical microscope to calculate the average value of the particle size of each conductive particle; or it can be obtained using a particle size distribution measuring device. In the observation using an electron microscope or an optical microscope, the particle size of each conductive particle is obtained as a particle size based on an equivalent circle diameter. In the observation using an electron microscope or an optical microscope, the average particle size based on an equivalent circle diameter of any 50 conductive particles is approximately equal to the average particle size based on an equivalent spherical diameter. In the particle size distribution measuring device, the particle size of each conductive particle is obtained as a particle size based on an equivalent spherical diameter. The average particle size of the conductive particles is preferably calculated using a particle size distribution measuring device.

[0063] The coefficient of variation (CV value) of the particle size of the conductive particles is preferably 10% or less, more preferably 5% or less. When the coefficient of variation of the particle size of the conductive particles is equal to or less than the upper limit, the contact area between the conductive particles and the electrode can be sufficiently increased.

[0064] The coefficient of variation (CV value) can be determined in the following manner.

[0065] CV value (%) = (ρ / Dn) × 100

[0066] ρ: Standard deviation (SD) of particle diameter of conductive particles

[0067] Dn: average value of particle size of conductive particles

[0068] The shape of the conductive particles is not particularly limited. The conductive particles may be spherical or may be other than spherical, such as flat.

[0069] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings.

[0070] Figure 1 This is a cross-sectional view showing the conductive particles according to the first embodiment of the present invention.

[0071] Figure 1 The conductive particles 1 shown include substrate particles 2 and conductive parts 3 disposed on the surfaces of the substrate particles 2. In the first embodiment, the conductive parts 3 are in contact with the surfaces of the substrate particles 2. The conductive particles 1 are coated particles in which the surfaces of the substrate particles 2 are coated with the conductive parts 3.

[0072] The conductive part 3 as a whole has: a first conductive part 3A disposed on the surface of the substrate particle 2, and a second conductive part (solder part) 3B disposed on the surface of the first conductive part 3A. The first conductive part 3A is disposed on the surface of the substrate particle 2. The first conductive part 3A is disposed between the substrate particle 2 and the second conductive part (solder part) 3B. The first conductive part 3A is in contact with the substrate particle 2. The second conductive part (solder part) 3B is in contact with the first conductive part 3A. Therefore, the first conductive part 3A is disposed on the surface of the substrate particle 2, and the second conductive part (solder part) 3B is disposed on the surface of the first conductive part 3A. In the conductive particles, the substrate particles may be completely covered by the first conductive part or may not be completely covered. The substrate particles may have a portion not covered by the first conductive part. The first conductive part and the second conductive part (solder part) may be formed as different conductive parts or may be formed as the same conductive part. The second conductive part (solder part) is formed by solder. The second conductive portion (solder portion) is preferably a solder particle described below. In the conductive particle, the first conductive portion is preferably arranged on the surface of the substrate particle, and the solder particle is preferably arranged on the surface of the first conductive portion.

[0073] In the conductive particle 1, the conductive part 3 includes a component that can cause metal diffusion at 400°C or below, or the conductive part 3 can be melt-deformed at 400°C or below. The conductive part 3 may include a component that can cause metal diffusion at 400°C or below, or the conductive part 3 may be melt-deformed at 400°C or below. The conductive part 3 may include a component that can cause metal diffusion at 400°C or below, and the conductive part 3 may be melt-deformed at 400°C or below. In the conductive particle 1, the second conductive part 3B (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 1, the second conductive part 3B (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the first conductive part may be a component that can cause metal diffusion at 400°C or below, or the first conductive part may be melt-deformed at 400°C or below. In the conductive particles, the first conductive portion and the second conductive portion (solder portion) may be components capable of metal diffusion at 400° C. or lower, or may be capable of melting and deforming at 400° C. or lower.

[0074] Figure 2 It is a cross-sectional view showing the conductive particles according to the second embodiment of the present invention.

[0075] Figure 2The conductive particles 11 shown include substrate particles 2 and conductive parts 12 disposed on the surfaces of the substrate particles 2. In the second embodiment, the conductive parts 12 are in contact with the surfaces of the substrate particles 2. The conductive particles 11 are coated particles in which the surfaces of the substrate particles 2 are coated with the conductive parts 12.

[0076] The conductive particles 1 and 11 differ only in the first conductive part. That is, the conductive particle 1 has a first conductive part 3A with a single layer structure, whereas the conductive particle 11 has a first conductive part with a two-layer structure consisting of a 1a conductive part 12A and a 1b conductive part 12B.

[0077] The conductive part 12 as a whole has: the conductive part 12A 1a arranged on the surface of the substrate particle 2, the conductive part 12B 1b arranged on the surface of the conductive part 12A 1a, and the second conductive part (solder part) 12C arranged on the surface of the conductive part 12B 1b. The conductive part 12A 1a is arranged on the surface of the substrate particle 2. The conductive part 12B 1b is arranged on the surface of the conductive part 12A 1a. The conductive part 12A 1a and the conductive part 12B 1b are arranged between the substrate particle 2 and the second conductive part (solder part) 12C. The conductive part 12A 1a is in contact with the substrate particle 2. The second conductive part (solder part) 12C is in contact with the conductive part 12B 1b. Therefore, the conductive part 12A 1a is arranged on the surface of the substrate particle 2, the conductive part 12B 1b is arranged on the surface of the conductive part 12A 1a, and the second conductive part (solder part) 12C is arranged on the surface of the conductive part 12B 1b. In the conductive particles, the substrate particles may be completely covered by the conductive part 1a and the conductive part 1b, or may not be completely covered. The substrate particles may have a portion that is not covered by the conductive part 1a and the conductive part 1b. The conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be formed as different conductive parts, or may be formed as the same conductive part. The second conductive part (solder part) is formed by solder. The second conductive part (solder part) is preferably a solder particle described later. In the conductive particles, it is preferred that the conductive part 1a is arranged on the surface of the substrate particles, the conductive part 1b is arranged on the surface of the conductive part 1a, and the solder particles are arranged on the surface of the conductive part 1b.

[0078] In the conductive particle 11, the conductive part 12 includes a component that can cause metal diffusion at 400°C or below, or the conductive part 12 can be melt-deformed at 400°C or below. The conductive part 12 may include a component that can cause metal diffusion at 400°C or below, or the conductive part 12 may be melt-deformed at 400°C or below. The conductive part 12 may include a component that can cause metal diffusion at 400°C or below, and the conductive part 12 may be melt-deformed at 400°C or below. In the conductive particle 11, the second conductive part 12C (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 11, the second conductive part 12C (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the conductive part 1a or the conductive part 1b may be a component that can cause metal diffusion at 400°C or below, or the conductive part 1a or the conductive part 1b may be melt-deformed at 400°C or below. Among the conductive particles, the conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be components capable of metal diffusion below 400°C, or the conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be capable of melting and deforming below 400°C.

[0079] Figure 3 It is a cross-sectional view which shows the electroconductive particle which concerns on 3rd Embodiment of this invention.

[0080] Figure 3 The conductive particles 21 shown include substrate particles 2 and conductive parts 22 disposed on the surfaces of the substrate particles 2. In the third embodiment, the conductive parts 22 are in contact with the surfaces of the substrate particles 2. The conductive particles 21 are coated particles in which the surfaces of the substrate particles 2 are coated with the conductive parts 22.

[0081] The conductive particles 1 and 21 differ only in the shape of the second conductive portion (solder portion). That is, in the conductive particle 1, the second conductive portion (solder portion) 3B has a shape of a part of a sphere, whereas in the conductive particle 21, the second conductive portion (solder portion) 22B has a needle shape and a rotational parabola shape.

[0082] The conductive part 22 as a whole has: a first conductive part 22A disposed on the surface of the substrate particle 2, and a second conductive part (solder part) 22B disposed on the surface of the first conductive part 22A. The first conductive part 22A is disposed on the surface of the substrate particle 2. The first conductive part 22A is disposed between the substrate particle 2 and the second conductive part (solder part) 22B. The first conductive part 22A is in contact with the substrate particle 2. The second conductive part (solder part) 22B is in contact with the first conductive part 22A. Therefore, the first conductive part 22A is disposed on the surface of the substrate particle 2, and the second conductive part (solder part) 22B is disposed on the surface of the first conductive part 22A. In the conductive particles, the substrate particles may be completely covered by the first conductive part, or may not be completely covered. The substrate particles may have a portion not covered by the first conductive part. The first conductive part and the second conductive part (solder part) may be formed as different conductive parts, or may be formed as the same conductive part. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably solder particles described below.

[0083] In the conductive particle 21, the conductive portion 22 includes a component that can cause metal diffusion at 400°C or below, or the conductive portion 22 can be melt-deformed at 400°C or below. The conductive portion 22 may include a component that can cause metal diffusion at 400°C or below, or the conductive portion 22 may be melt-deformed at 400°C or below. The conductive portion 22 may include a component that can cause metal diffusion at 400°C or below, and the conductive portion 22 may be melt-deformed at 400°C or below. In the conductive particle 21, the second conductive portion 22B (solder portion) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 21, the second conductive portion 22B (solder portion) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the first conductive portion may be a component that can cause metal diffusion at 400°C or below, or the first conductive portion may be melt-deformed at 400°C or below. In the conductive particles, the first conductive portion and the second conductive portion (solder portion) may be components capable of metal diffusion at 400° C. or lower, or may be capable of melting and deforming at 400° C. or lower.

[0084] Figure 4 It is a cross-sectional view showing the conductive particles according to the fourth embodiment of the present invention.

[0085] Figure 4 The conductive particles 31 shown include substrate particles 2 and conductive parts 32 disposed on the surfaces of the substrate particles 2. In the fourth embodiment, the conductive parts 32 are in contact with the surfaces of the substrate particles 2. The conductive particles 31 are coated particles in which the surfaces of the substrate particles 2 are coated with the conductive parts 32.

[0086] The conductive particles 21 and 31 differ only in the conductive portion. That is, in the conductive particle 21, the conductive portion 22 is formed of the first conductive portion 22A and the second conductive portion (solder portion) 22B, whereas in the conductive particle 31, the conductive portion 32 is formed of the first conductive portion 32A, the second conductive portion (solder portion) 32B, and the third conductive portion 32C.

[0087] The conductive part 32 as a whole has: a first conductive part 32A arranged on the surface of the substrate particle 2, a second conductive part (solder part) 32B arranged on the surface of the first conductive part 32A, and a third conductive part 32C arranged on the surfaces of the first conductive part 32A and the second conductive part (solder part) 32B. The first conductive part 32A is arranged on the surface of the substrate particle 2. The third conductive part 32C is arranged on the surfaces of the first conductive part 32A and the second conductive part (solder part) 32B. The first conductive part 32A and the second conductive part (solder part) 32B are arranged between the substrate particle 2 and the third conductive part 32C. The first conductive part 32A is in contact with the substrate particle 2. The second conductive part (solder part) 32B is in contact with the first conductive part 32A. The third conductive part 32C is in contact with the first conductive part 32A and the second conductive part (solder part) 32B. Therefore, the first conductive part 32A is arranged on the surface of the substrate particle 2, the second conductive part (solder part) 32B is arranged on the surface of the first conductive part 32A, and the third conductive part 32C is arranged on the surface of the first conductive part 32A and the second conductive part (solder part) 32B. In the conductive particles, the substrate particles may be completely covered by the first conductive part, or may not be completely covered. The substrate particles may have a part that is not covered by the first conductive part. In the conductive particles, the substrate particles may be completely covered by the third conductive part, or may not be completely covered. The substrate particles may have a part that is not covered by the third conductive part. The first conductive part, the second conductive part (solder part) and the third conductive part may be formed as different conductive parts, or may be formed as the same conductive part. The second conductive part (solder part) is formed by solder. The second conductive part (solder part) is preferably a solder particle described later. In the conductive particles, it is preferred that the first conductive portion is arranged on the surface of the substrate particle, the solder particles are arranged on the surface of the first conductive portion, and the third conductive portion is arranged on the surfaces of the first conductive portion and the solder particles.

[0088] In the conductive particle 31, the conductive portion 32 includes a component that can cause metal diffusion at 400°C or below, or the conductive portion 32 can be melt-deformed at 400°C or below. The conductive portion 32 may include a component that can cause metal diffusion at 400°C or below, or the conductive portion 32 may be melt-deformed at 400°C or below. The conductive portion 32 may include a component that can cause metal diffusion at 400°C or below, and the conductive portion 32 may be melt-deformed at 400°C or below. In the conductive particle 31, the second conductive portion 32B (solder portion) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 31, the second conductive portion 32B (solder portion) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the first conductive portion may be a component that can cause metal diffusion at 400°C or below, or the first conductive portion may be melt-deformed at 400°C or below. In the conductive particles, the third conductive part may be a component that can undergo metal diffusion at 400° C. or less, or the third conductive part may be melt-deformed at 400° C. or less. In the conductive particles, the first conductive part, the second conductive part (solder part), and the third conductive part may be a component that can undergo metal diffusion at 400° C. or less, or the first conductive part, the second conductive part (solder part), and the third conductive part may be melt-deformed at 400° C. or less.

[0089] Figure 5 It is a cross-sectional view showing the conductive particle according to the fifth embodiment of the present invention.

[0090] Figure 5 The conductive particles 41 shown include substrate particles 2, conductive portions 42 disposed on the surface of the substrate particles 2, and metal colloidal precipitates 43 disposed on the surface of the conductive portions 42. In the fifth embodiment, the conductive portions 42 are in contact with the surface of the substrate particles 2. The conductive particles 41 are coated particles in which the surface of the substrate particles 2 is coated with the conductive portions 42.

[0091] The conductive particles 1 and 41 differ only in the presence or absence of metal colloidal precipitates 43. That is, in the conductive particles 1, no metal colloidal precipitates are arranged on the surface of the conductive portion 3, whereas in the conductive particles 41, metal colloidal precipitates 43 are arranged on the surface of the conductive portion 42.

[0092] The conductive part 42 as a whole has: a first conductive part 42A disposed on the surface of the substrate particle 2, and a second conductive part (solder part) 42B disposed on the surface of the first conductive part 42A. The first conductive part 42A is disposed on the surface of the substrate particle 2. The first conductive part 42A is disposed between the substrate particle 2 and the second conductive part (solder part) 42B. The first conductive part 42A is in contact with the substrate particle 2. The second conductive part (solder part) 42B is in contact with the first conductive part 42A. Therefore, the first conductive part 42A is disposed on the surface of the substrate particle 2, and the second conductive part (solder part) 42B is disposed on the surface of the first conductive part 42A. In the conductive particles, the substrate particles may be completely covered by the first conductive part, or may not be completely covered. The substrate particles may have a portion not covered by the first conductive part. The first conductive part and the second conductive part (solder part) may be formed as different conductive parts, or may be formed as the same conductive part. The second conductive part (solder part) is formed of solder. The second conductive part (solder part) is preferably a solder particle described later. In the conductive particles, the first conductive part is preferably arranged on the surface of the substrate particle, and the solder particle is preferably arranged on the surface of the first conductive part.

[0093] A metal colloid precipitate 43 is arranged on the surface of the conductive part 42. The metal colloid precipitate may be arranged only on the surface of the first conductive part, may be arranged only on the surface of the second conductive part (solder part), or may be arranged on the surfaces of the first conductive part and the second conductive part (solder part). The metal colloid precipitate is preferably arranged only on the surface of the second conductive part (solder part), preferably arranged only on the surface of the solder particles. In the conductive particles, the conductive part may be completely covered by the metal colloid precipitate, or may not be completely covered. The conductive part may have a portion that is not covered by the metal colloid precipitate.

[0094] In the conductive particle 41, the conductive part 42 includes a component that can cause metal diffusion at 400°C or below, or the conductive part 42 can be melt-deformed at 400°C or below. The conductive part 42 may include a component that can cause metal diffusion at 400°C or below, or the conductive part 42 may be melt-deformed at 400°C or below. The conductive part 42 may include a component that can cause metal diffusion at 400°C or below, and the conductive part 42 may be melt-deformed at 400°C or below. In the conductive particle 41, the second conductive part 42B (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 41, the second conductive part 42B (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the first conductive part may be a component that can cause metal diffusion at 400°C or below, or the first conductive part may be melt-deformed at 400°C or below. In the conductive particles, the first conductive portion and the second conductive portion (solder portion) may be components capable of metal diffusion at 400° C. or lower, or may be capable of melting and deforming at 400° C. or lower.

[0095] Figure 6 It is a cross-sectional view showing the conductive particles according to the sixth embodiment of the present invention.

[0096] Figure 6 The conductive particles 51 shown include substrate particles 2, conductive portions 52 disposed on the surface of the substrate particles 2, and metal colloid precipitates 53 disposed on the surface of the conductive portions 52. In the sixth embodiment, the conductive portions 52 are in contact with the surface of the substrate particles 2. The conductive particles 51 are coated particles in which the surface of the substrate particles 2 is coated with the conductive portions 52.

[0097] The conductive particles 11 and 51 differ only in the presence or absence of metal colloidal precipitates 53. That is, in the conductive particles 11, no metal colloidal precipitates are arranged on the surface of the conductive portion 12, whereas in the conductive particles 51, metal colloidal precipitates 53 are arranged on the surface of the conductive portion 52.

[0098] The conductive part 52 as a whole has: the 1a conductive part 52A arranged on the surface of the substrate particle 2, the 1b conductive part 52B arranged on the surface of the 1a conductive part 52A, and the second conductive part (solder part) 52C arranged on the surface of the 1b conductive part 52B. The 1a conductive part 52A is arranged on the surface of the substrate particle 2. The 1b conductive part 52B is arranged on the surface of the 1a conductive part 52A. The 1a conductive part 52A and the 1b conductive part 52B are arranged between the substrate particle 2 and the second conductive part (solder part) 52C. The 1a conductive part 52A is in contact with the substrate particle 2. The second conductive part (solder part) 52C is in contact with the 1b conductive part 52B. Therefore, the 1a conductive part 52A is arranged on the surface of the substrate particle 2, the 1b conductive part 52B is arranged on the surface of the 1a conductive part 52A, and the second conductive part (solder part) 52C is arranged on the surface of the 1b conductive part 52B. In the conductive particles, the substrate particles may be completely covered by the conductive part 1a and the conductive part 1b, or may not be completely covered. The substrate particles may have a portion that is not covered by the conductive part 1a and the conductive part 1b. The conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be formed as different conductive parts, or may be formed as the same conductive part. The second conductive part (solder part) is formed by solder. The second conductive part (solder part) is preferably a solder particle described later. In the conductive particles, it is preferred that the conductive part 1a is arranged on the surface of the substrate particles, the conductive part 1b is arranged on the surface of the conductive part 1a, and the solder particles are arranged on the surface of the conductive part 1b.

[0099] A metal colloid precipitate 53 is arranged on the surface of the conductive part 52. The metal colloid precipitate may be arranged only on the surface of the 1b conductive part, may be arranged only on the surface of the 2nd conductive part (solder part), or may be arranged on the surfaces of the 1b conductive part and the 2nd conductive part (solder part). The metal colloid precipitate is preferably arranged only on the surface of the 2nd conductive part (solder part), preferably arranged only on the surface of the solder particles. In the conductive particles, the conductive part may be completely covered by the metal colloid precipitate, or may not be completely covered. The conductive part may have a portion that is not covered by the metal colloid precipitate.

[0100] In the conductive particle 51, the conductive part 52 includes a component that can cause metal diffusion at 400°C or below, or the conductive part 52 can be melt-deformed at 400°C or below. The conductive part 52 may include a component that can cause metal diffusion at 400°C or below, or the conductive part 52 may be melt-deformed at 400°C or below. The conductive part 52 may include a component that can cause metal diffusion at 400°C or below, and the conductive part 52 may be melt-deformed at 400°C or below. In the conductive particle 51, the second conductive part 52C (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 51, the second conductive part 52C (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the conductive part 1a or the conductive part 1b may be a component that can cause metal diffusion at 400°C or below, or the conductive part 1a or the conductive part 1b may be melt-deformed at 400°C or below. Among the conductive particles, the conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be components capable of metal diffusion below 400°C, or the conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be capable of melting and deforming below 400°C.

[0101] Figure 7 This is a cross-sectional view showing conductive particles according to a seventh embodiment of the present invention.

[0102] Figure 7 The conductive particles 61 shown include substrate particles 2, conductive portions 62 disposed on the surface of the substrate particles 2, and metal films 63 disposed on the surface of the conductive portions 62. In the seventh embodiment, the conductive portions 62 are in contact with the surface of the substrate particles 2. The conductive particles 61 are coated particles in which the surface of the substrate particles 2 is coated with the conductive portions 62.

[0103] The conductive particles 1 and 61 differ only in the presence or absence of the metal film 63. That is, the conductive particles 1 do not have a metal film on the surface of the conductive portion 3, whereas the conductive particles 61 have a metal film 63 on the surface of the conductive portion 62.

[0104] The conductive part 62 as a whole has: a first conductive part 62A disposed on the surface of the substrate particle 2, and a second conductive part (solder part) 62B disposed on the surface of the first conductive part 62A. The first conductive part 62A is disposed on the surface of the substrate particle 2. The first conductive part 62A is disposed between the substrate particle 2 and the second conductive part (solder part) 62B. The first conductive part 62A is in contact with the substrate particle 2. The second conductive part (solder part) 62B is in contact with the first conductive part 62A. Therefore, the first conductive part 62A is disposed on the surface of the substrate particle 2, and the second conductive part (solder part) 62B is disposed on the surface of the first conductive part 62A. In the conductive particles, the substrate particles may be completely covered by the first conductive part, or may not be completely covered. The substrate particles may have a portion not covered by the first conductive part. The first conductive part and the second conductive part (solder part) may be formed as different conductive parts, or may be formed as the same conductive part. The second conductive part (solder part) is formed of solder. The second conductive part (solder part) is preferably a solder particle described later. In the conductive particles, the first conductive part is preferably arranged on the surface of the substrate particle, and the solder particle is preferably arranged on the surface of the first conductive part.

[0105] A metal film 63 is disposed on the surface of the conductive part 62. The metal film may be disposed only on the surface of the first conductive part, may be disposed only on the surface of the second conductive part (solder part), or may be disposed on the surfaces of the first conductive part and the second conductive part (solder part). The metal film is preferably disposed only on the surface of the second conductive part (solder part), and is preferably disposed only on the surface of the solder particles. In the conductive particles, the conductive part may be completely covered by the metal film or may not be completely covered. The conductive part may have a portion that is not covered by the metal film.

[0106] In the conductive particle 61, the conductive portion 62 includes a component that can cause metal diffusion at 400°C or below, or the conductive portion 62 can be melt-deformed at 400°C or below. The conductive portion 62 may include a component that can cause metal diffusion at 400°C or below, or the conductive portion 62 may be melt-deformed at 400°C or below. The conductive portion 62 may include a component that can cause metal diffusion at 400°C or below, and the conductive portion 62 may be melt-deformed at 400°C or below. In the conductive particle 61, the second conductive portion 62B (solder portion) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 61, the second conductive portion 62B (solder portion) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the first conductive portion may be a component that can cause metal diffusion at 400°C or below, or the first conductive portion may be melt-deformed at 400°C or below. In the conductive particles, the first conductive portion and the second conductive portion (solder portion) may be components capable of metal diffusion at 400° C. or lower, or may be capable of melting and deforming at 400° C. or lower.

[0107] Figure 8 It is a cross-sectional view showing the conductive particles according to the eighth embodiment of the present invention.

[0108] Figure 8 The conductive particles 71 shown include substrate particles 2, conductive portions 72 disposed on the surface of the substrate particles 2, and metal films 73 disposed on the surface of the conductive portions 72. In the eighth embodiment, the conductive portions 72 are in contact with the surface of the substrate particles 2. The conductive particles 71 are coated particles in which the surface of the substrate particles 2 is coated with the conductive portions 72.

[0109] The conductive particles 11 and 71 differ only in the presence or absence of the metal film 73. That is, the conductive particles 11 do not have a metal film on the surface of the conductive portion 12, whereas the conductive particles 71 have a metal film 73 on the surface of the conductive portion 72.

[0110] The conductive part 72 as a whole has: the 1a conductive part 72A arranged on the surface of the substrate particle 2, the 1b conductive part 72B arranged on the surface of the 1a conductive part 72A, and the second conductive part (solder part) 72C arranged on the surface of the 1b conductive part 72B. The 1a conductive part 72A is arranged on the surface of the substrate particle 2. The 1b conductive part 72B is arranged on the surface of the 1a conductive part 72A. The 1a conductive part 72A and the 1b conductive part 72B are arranged between the substrate particle 2 and the second conductive part (solder part) 72C. The 1a conductive part 72A is in contact with the substrate particle 2. The second conductive part (solder part) 72C is in contact with the 1b conductive part 72B. Therefore, the 1a conductive part 72A is arranged on the surface of the substrate particle 2, the 1b conductive part 72B is arranged on the surface of the 1a conductive part 72A, and the second conductive part (solder part) 72C is arranged on the surface of the 1b conductive part 72B. In the conductive particles, the substrate particles may be completely covered by the conductive part 1a and the conductive part 1b, or may not be completely covered. The substrate particles may have a portion that is not covered by the conductive part 1a and the conductive part 1b. The conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be formed as different conductive parts, or may be formed as the same conductive part. The second conductive part (solder part) is formed by solder. The second conductive part (solder part) is preferably a solder particle described later. In the conductive particles, it is preferred that the conductive part 1a is arranged on the surface of the substrate particles, the conductive part 1b is arranged on the surface of the conductive part 1a, and the solder particles are arranged on the surface of the conductive part 1b.

[0111] A metal film 73 is disposed on the surface of the conductive part 72. The metal film may be disposed only on the surface of the 1b conductive part, may be disposed only on the surface of the 2nd conductive part (solder part), or may be disposed on the surfaces of the 1b conductive part and the 2nd conductive part (solder part). The metal film is preferably disposed only on the surface of the 2nd conductive part (solder part), and is preferably disposed only on the surface of the solder particles. In the conductive particles, the conductive part may be completely covered by the metal film or may not be completely covered. The conductive part may have a portion that is not covered by the metal film.

[0112] In the conductive particle 71, the conductive part 72 includes a component that can cause metal diffusion at 400°C or below, or the conductive part 72 can be melt-deformed at 400°C or below. The conductive part 72 may include a component that can cause metal diffusion at 400°C or below, or the conductive part 72 may be melt-deformed at 400°C or below. The conductive part 72 may include a component that can cause metal diffusion at 400°C or below, and the conductive part 72 may be melt-deformed at 400°C or below. In the conductive particle 71, the second conductive part 72C (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle 71, the second conductive part 72C (solder part) is a component that can cause metal diffusion at 400°C or below. In the conductive particle, the conductive part 1a or the conductive part 1b may be a component that can cause metal diffusion at 400°C or below, or the conductive part 1a or the conductive part 1b may be melt-deformed at 400°C or below. Among the conductive particles, the conductive part 1a, the conductive part 1b and the second conductive part (solder part) may be components capable of metal diffusion at 400°C or below, or may be capable of melting and deforming at 400°C or below.

[0113] Other details of the conductive particles are described below. It should be noted that in the following description, "(meth)acrylic acid" refers to one or both of "acrylic acid" and "methacrylic acid", "(meth)acryloyloxy" refers to one or both of "acryloyloxy" and "methacryloyloxy", and "(meth)acrylate" refers to one or both of "acrylate" and "methacrylate".

[0114] (Base material particles)

[0115] The material of the substrate particles is not particularly limited. The material of the substrate particles can be an organic material or an inorganic material. As the substrate particles formed only by the organic material, resin particles and the like can be cited. As the substrate particles formed only by the inorganic material, inorganic particles other than metals and the like can be cited. As the substrate particles formed by both the organic material and the inorganic material, organic-inorganic hybrid particles and the like can be cited. From the viewpoint of further improving the compression characteristics of the substrate particles, the substrate particles are preferably resin particles or organic-inorganic hybrid particles, and more preferably resin particles.

[0116] Examples of the organic material include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenolic resin, melamine resin, benzoguanamine resin, urea formaldehyde resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene ether, polyacetal, polyimide, polyamideimide, polyetheretherketone, polyethersulfone, divinylbenzene polymers, and divinylbenzene copolymers. Examples of the divinylbenzene copolymers include divinylbenzene-styrene copolymers and divinylbenzene-(meth)acrylate copolymers. Since the compression characteristics of the substrate particles can be easily controlled within a suitable range, the material of the substrate particles is preferably a polymer obtained by polymerizing a polymerizable monomer having one or more ethylenically unsaturated groups.

[0117] When the substrate particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, examples of the polymerizable monomer having an ethylenically unsaturated group include non-crosslinkable monomers and crosslinkable monomers.

[0118] Examples of the non-crosslinking monomer include: vinyl compounds such as styrene, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; halogen-containing monomers such as vinyl chloride and vinyl fluoride; (meth)acrylic acid compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, and stearyl (meth)acrylate. (meth)acrylate compounds containing oxygen atoms such as 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; halogen-containing (meth)acrylate compounds such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; alpha-olefin compounds such as diisobutylene, isobutylene, linealene, ethylene, and propylene; conjugated diene compounds such as isoprene and butadiene.

[0119] Examples of the crosslinking monomer include vinyl monomers such as divinylbenzene, 1,4-divinyloxybutane, and divinyl sulfone as vinyl compounds; and (meth)acrylic acid compounds such as tetramethylolmethane tetra(meth)acrylate, polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate. As the allyl compound, triallyl (iso)cyanurate, triallyl trimellitate, diallyl phthalate, diallyl acrylamide, diallyl ether; as the silane compound, tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane , n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, diphenyldimethoxysilane and other silane alkoxy compounds; vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methylvinyldimethoxysilane, ethyl Polymerizable double-bond-containing silane alkoxides such as vinyl dimethoxysilane, methyl vinyl diethoxysilane, ethyl vinyl diethoxysilane, p-phenylvinyl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, 3-methacryloxypropyl triethoxysilane, and 3-acryloxypropyl trimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as single-end modified silicone oil, double-end silicone oil, and side-chain silicone oil; carboxyl-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride, etc.

[0120] Examples of the inorganic material include silicon dioxide, aluminum oxide, barium titanate, zirconium oxide, carbon black, silicate glass, borosilicate glass, lead glass, soda-lime glass, and alumina silicate glass.

[0121] The substrate particles may be organic-inorganic hybrid particles. The substrate particles may be core-shell particles. In the case where the substrate particles are organic-inorganic hybrid particles, the inorganic material of the substrate particles may include silica, alumina, barium titanate, zirconium oxide, carbon black, etc. The inorganic material is preferably not a metal. The substrate particles formed of silica are not particularly limited, and examples include substrate particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form cross-linked polymer particles and then firing as needed. Examples of the organic-inorganic hybrid particles include organic-inorganic hybrid particles formed by cross-linked alkoxysilyl polymers and acrylic resins, etc.

[0122] The organic-inorganic hybrid particles are preferably core-shell organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. The substrate particles are preferably organic-inorganic hybrid particles having an organic core and an inorganic shell disposed on the surface of the organic core.

[0123] Examples of the material of the organic core include the above-mentioned organic materials.

[0124] As the material of the inorganic shell, there can be mentioned: the inorganic substances mentioned as the material of the substrate particles, etc. The material of the inorganic shell is preferably silicon dioxide. The inorganic shell is preferably formed by the following method: after a metal alkoxide is made into a shell-like object on the surface of the core by a sol-gel method, the shell-like object is fired. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed by a silane alkoxide.

[0125] The particle size of the substrate particles is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 500 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle size of the substrate particles is above the lower limit and below the upper limit, it can be further applied to obtain conductive particles. When the particle size of the substrate particles is above the lower limit and below the upper limit, the contact area between the conductive particles and the electrode can be fully increased, and it is not easy to form conductive particles that have been condensed when forming the conductive portion, and the conductive portion is not easy to peel off from the surface of the substrate particles.

[0126] The particle size of the substrate particles is particularly preferably 1 μm to 50 μm. When the particle size of the substrate particles is within the range of 1 μm to 50 μm, it is not easy to form agglomeration when forming a conductive portion on the surface of the substrate particles, or it is not easy to form conductive particles that have been agglomerated. In addition, when the particle size of the substrate particles is within the range of 1 μm to 50 μm, it can be further suitable for obtaining conductive particles.

[0127] The particle size of the substrate particles refers to the diameter when the substrate particles are spherical, and refers to the diameter when the substrate particles are not spherical, assuming a sphere having a volume equivalent to the substrate particles.

[0128] The particle size of the substrate particles represents the number average particle size. The particle size of the substrate particles can be obtained by observing any 50 substrate particles by an electron microscope or an optical microscope, and calculating the average value of the particle size of each substrate particle; or using a particle size distribution measuring device. In the observation using an electron microscope or an optical microscope, the particle size of each substrate particle is obtained as a particle size based on an equivalent circle diameter. In the observation using an electron microscope or an optical microscope, the average particle size based on an equivalent circle diameter of any 50 substrate particles is approximately equal to the average particle size based on an equivalent spherical diameter. In the case of a particle size distribution measuring device, the particle size of each substrate particle is obtained as a particle size based on an equivalent spherical diameter. The average particle size of the substrate particles is preferably calculated using a particle size distribution measuring device. In the conductive particles, when the particle size of the substrate particles is measured, for example, it can be measured in the following manner.

[0129] In such a way that the content of conductive particles is 30% by weight, it is added to "TECHNOVIT4000" manufactured by Kulzer and dispersed to prepare an embedded resin body for conductive particle inspection. An ion milling device (HITACHI HIGH-TECHNOLOGIES "IM4000") is used to cut out the cross section of the conductive particles by dispersing them near the center of the conductive particles in the embedded resin body for inspection. In addition, using a field emission scanning electron microscope (FE-SEM), 50 conductive particles are randomly selected to observe the substrate particles of each conductive particle. The particle size of the substrate particles in each conductive particle is measured, and they are arithmetic averaged and set as the particle size of the substrate particles.

[0130] (Conductive part)

[0131] The electroconductive particle of this invention is equipped with: substrate particle and the electroconductive part arrange|positioned on the surface of the said substrate particle. It is preferable that the said electroconductive part contains metal.

[0132] In the conductive particles, the conductive portion includes a component that can cause metal diffusion at 400°C or less, or the conductive portion can be melt-deformed at 400°C or less. By lowering the temperature at which metal diffusion can occur, metal bonding can be more easily formed between the bonding parts of electrodes, etc. Therefore, the temperature at which metal diffusion can occur is preferably 350°C or less, more preferably 300°C or less, further preferably 250°C or less, and particularly preferably 200°C or less. The temperature at which metal diffusion can occur can be controlled by the type of metal.

[0133] In addition, the conductive part is preferably capable of melting and deforming at a temperature below 400°C. The conductive part is preferably capable of melting and deforming at a temperature below 350°C, more preferably capable of melting and deforming at a temperature below 300°C, further preferably capable of melting and deforming at a temperature below 250°C, and particularly preferably capable of melting and deforming at a temperature below 200°C. When the melting deformation temperature of the conductive part is within the preferred range, the melting deformation temperature can be lowered, the energy consumption during heating can be suppressed, and thermal degradation of the connection object parts and the like can be suppressed. The melting deformation temperature of the conductive part can be controlled by the type of metal of the conductive part. The conductive part may have a portion exceeding 200°C, a portion exceeding 250°C, a portion exceeding 300°C, a portion exceeding 350°C, and a portion exceeding 400°C.

[0134] The metal constituting the conductive portion is not particularly limited. Examples of the metal constituting the conductive portion include gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and alloys thereof. In addition, examples of the metal constituting the conductive portion include tin-doped indium oxide (ITO) and solder. The metal constituting the conductive portion may be used alone or in combination of two or more.

[0135] In the present invention, the metal constituting the conductive portion is preferably selected so that the conductive portion contains a component that can cause metal diffusion at 400° C. or less, and so that the conductive portion can be melt-deformed at 400° C. or less. The conductive portion preferably contains solder, and preferably has a solder portion. The solder portion is formed of solder. The conductive portion preferably has a solder portion formed of solder.

[0136] From the viewpoint of more effectively reducing the connection resistance, the conductive portion preferably contains nickel, gold, palladium, silver, copper, tin, or an alloy containing tin, and more preferably contains nickel, gold, palladium, tin, or an alloy containing tin.

[0137] In 100 wt % of the conductive part containing silver, the content of silver is preferably 0.1 wt % or more, more preferably 1 wt % or more, preferably 100 wt % or less, and more preferably 90 wt % or less. The content of silver may be 80 wt % or less, 60 wt % or less, 40 wt % or less, 20 wt % or less, or 10 wt % or less. When the content of silver is above the lower limit and below the upper limit, the aggregation of the conductive particles can be further effectively suppressed.

[0138] In 100 wt % of the conductive portion containing copper, the content of copper is preferably 0.1 wt % or more, more preferably 1 wt % or more, preferably 100 wt % or less, and more preferably 90 wt % or less. The content of copper may be 80 wt % or less, 60 wt % or less, 40 wt % or less, 20 wt % or less, or 10 wt % or less. When the content of copper is above the lower limit and below the upper limit, the aggregation of the conductive particles can be further effectively suppressed.

[0139] In 100 wt % of the conductive portion comprising tin or a tin-containing alloy, the content of tin or a tin-containing alloy is preferably 20 wt % or more, more preferably 50 wt % or more, and particularly preferably 90 wt % or more. When the content of tin or the tin-containing alloy is above the lower limit, aggregation of the conductive particles can be further effectively suppressed.

[0140] The solder is preferably a metal with a melting point of 450°C or less (low melting point metal). The low melting point metal refers to a metal with a melting point of 450°C or less. The melting point of the low melting point metal is preferably 300°C or less, more preferably 160°C or less. In addition, the solder contains tin. In 100% by weight of the metal contained in the solder, the tin content is preferably 30% by weight or more, more preferably 40% by weight or more, further preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the tin content in the solder is above the lower limit, the conduction reliability is further improved.

[0141] It should be noted that the contents of the nickel, copper and tin can be measured using a high-frequency inductively coupled plasma atomic emission spectrometer ("ICP-AES" manufactured by Horiba, Ltd.) or a fluorescent X-ray analyzer ("EDX-800HS" manufactured by Shimadzu Corporation).

[0142] By using the solder, the solder is melted and joined to the electrode, so that the solder conducts between the electrodes. For example, the solder and the electrode are easily in surface contact rather than point contact, so the connection resistance becomes lower. In addition, by using the solder, the bonding strength between the solder and the electrode is improved, and as a result, the solder and the electrode are further less likely to be peeled off, further effectively improving the conduction reliability.

[0143] The low melting point metal constituting the solder is not particularly limited. The low melting point metal is preferably tin or a tin-containing alloy. The alloy may include: tin-silver alloy, tin-copper alloy, tin-silver-copper alloy, tin-bismuth alloy, tin-zinc alloy, tin-indium alloy, etc. From the viewpoint of excellent wettability to the electrode, the low melting point metal is preferably tin, tin-silver alloy, tin-silver-copper alloy, tin-bismuth alloy, tin-indium alloy, more preferably tin-bismuth alloy, tin-indium alloy.

[0144] The solder is preferably a filler material having a liquidus of 450°C or less based on JIS Z3001: Welding Terms. Examples of the composition of the solder include metal compositions containing zinc, gold, silver, lead, copper, tin, bismuth, indium, and the like. The solder is preferably a tin-indium type (117°C eutectic) or a tin-bismuth type (139°C eutectic) having a low melting point and being lead-free. That is, the solder preferably does not contain lead, and preferably contains tin and indium or contains tin and bismuth.

[0145] In order to further improve the bonding strength, the solder may contain metals such as nickel, copper, antimony, aluminum, zinc, iron, gold, titanium, phosphorus, germanium, tellurium, cobalt, bismuth, manganese, chromium, molybdenum, and palladium. In addition, from the viewpoint of further improving the bonding strength, the solder preferably contains nickel, copper, antimony, aluminum, or zinc. From the viewpoint of further improving the bonding strength, the content of these metals for improving the bonding strength is preferably 0.0001% by weight or more, and preferably 1% by weight or less in 100% by weight of the solder.

[0146] The conductive portion may be formed of one layer. The conductive portion may be formed of multiple layers. That is, the conductive portion may have a laminated structure of more than two layers. From the viewpoint of further effectively improving the conduction reliability, the conductive portion preferably has a laminated structure of more than two layers.

[0147] The method for forming the conductive portion on the surface of the substrate particle is not particularly limited. As the method for forming the conductive portion, the following methods can be cited. A method based on electroless plating. A method based on electroplating. A method based on physical impact. A method based on a mechanochemical reaction. A method based on physical evaporation or physical adsorption. A method in which a paste comprising metal powder or metal powder and an adhesive is applied to the surface of substrate particles. The method for forming the conductive portion is preferably a method based on electroless plating, electroplating or physical impact. As the method based on physical evaporation, methods such as vacuum evaporation, ion plating and ion sputtering can be cited. In addition, as the method based on physical impact, THETACOMPOSER (manufactured by TOKUJU) and the like can be used.

[0148] The thickness of the conductive portion is preferably 10 nm or more, more preferably 500 nm or more, preferably 10 μm or less, more preferably 5 μm or less, further preferably 1 μm or less, and particularly preferably 800 nm or less. In the case where the conductive portion has a laminated structure of more than two layers, the thickness of the conductive portion refers to the thickness of the conductive portion as a whole. When the thickness of the conductive portion is above the lower limit and below the upper limit, the agglomeration of the conductive particles can be further effectively suppressed. In addition, when the thickness of the conductive portion is above the lower limit and below the upper limit, sufficient conductivity can be obtained and the conductive particles can be prevented from hardening.

[0149] When the conductive portion has a laminated structure of two or more layers, the thickness of the conductive portion of the outermost layer is preferably 10 nm or more, more preferably 500 nm or more, preferably 10 μm or less, more preferably 5 μm or less, further preferably 1 μm or less, and particularly preferably 800 nm or less. When the thickness of the conductive portion of the outermost layer is above the lower limit and below the upper limit, aggregation of conductive particles can be further effectively suppressed.

[0150] The thickness of the conductive portion can be measured by observing the cross section of the conductive particles using, for example, a transmission electron microscope (TEM). The thickness of the conductive portion is preferably the thickness of the portion where the thickness of the conductive portion is the largest in any conductive particle. The thickness of the conductive portion is preferably obtained by calculating the average value of the thickness of the conductive portion of each conductive particle for any 10 conductive particles.

[0151] Solder particles:

[0152] In the conductive particle, the conductive portion has a solder portion. The conductive portion has a solder portion formed of solder.

[0153] From the viewpoint of being able to more effectively suppress the aggregation of the conductive particles, the solder portion is preferably a solder particle. In the conductive particles, the conductive portion preferably has a solder particle. For example, Figure 1 The second conductive portion (solder portion) 3B in Figure 2 The second conductive portion (solder portion) 12C, Figure 3 The second conductive portion (solder portion) 22B and Figure 4 The second conductive portion (solder portion) 32B in is preferably solder particles. Figure 5 The second conductive portion (solder portion) 42B in Figure 6 The second conductive portion (solder portion) 52C in Figure 7 The second conductive portion (solder portion) 62B and Figure 8 The second conductive portion (solder portion) 72C in the embodiment is preferably solder particles.

[0154] The solder particles are different from the protrusions described later. The solder particles can form a metal bond between the joining parts of electrodes, etc. The solder particles are used to achieve joining with electrodes, etc. The conductive part can easily form a metal bond between the joining parts of electrodes, etc. by having the solder particles, so it is not necessary to melt the entire conductive part during joining. As a result, even when the thickness of the conductive part is thin, the conduction reliability between the electrodes can be improved. In addition, it is not necessary to increase the thickness of the conductive part, so the coagulation of the conductive particles can be effectively suppressed.

[0155] In addition, the solder particles are relatively small, so the outer surface of the solder particles can be less likely to be oxidized, and the influence of the oxide film can be suppressed. Therefore, the solder particles can be further easily formed into a metal bond between the joining parts of the electrodes, etc. On the other hand, in the case where the conductive particles have a solder layer coated with solder instead of the solder particles, the outer surface of the solder layer is easily oxidized, and it is difficult to suppress the influence of the oxide film. Therefore, it is impossible to easily form a metal bond between the joining parts of the electrodes, etc., and countermeasures such as thickening the solder layer need to be taken, which makes it difficult to suppress the coagulation of the conductive particles.

[0156] The shape of the solder particles is not particularly limited. The shape of the solder particles is preferably a needle-like shape or a part of a sphere. The needle-like shape is preferably a pyramidal shape, a conical shape, or a rotational parabola shape, more preferably a conical shape or a rotational parabola shape, and further preferably a conical shape. The shape of the solder particles may be a pyramidal shape, a conical shape, or a rotational parabola shape.

[0157] The material of the solder particles is not particularly limited. The solder particles are preferably made of metal. The material of the solder particles preferably includes a tin-containing alloy, or pure tin, or includes tin in a state different from the tin-containing alloy and in a state different from pure tin. The material of the solder particles may include a tin-containing alloy or pure tin. The material of the solder particles may be a tin-containing alloy or pure tin. The material of the solder particles may include tin in a state different from the tin-containing alloy and in a state different from pure tin. From the viewpoint of being able to further effectively inhibit the aggregation of conductive particles, the material of the solder particles is more preferably pure tin. It should be noted that the material of the solder particles is pure tin, which means that the content of tin in 100% by weight of the material of the solder particles is 90% by weight or more. In 100% by weight of the material of the solder particles, the content of tin may be less than 90% by weight, may be less than 80% by weight, may be less than 75% by weight, or may be less than 70% by weight.

[0158] In 100 wt % of the solder particles containing tin, the content of tin is preferably 20 wt % or more, more preferably 40 wt % or more, further preferably 90 wt % or more, preferably 99.5 wt % or less, and more preferably 99 wt % or less. When the content of tin is above the lower limit and below the upper limit, the aggregation of the conductive particles can be further effectively suppressed. When the content of tin is above the lower limit and below the upper limit, the solder particles can be more easily metal-bonded between the bonding parts of the electrodes, etc.

[0159] The height of the solder particles is preferably 10 nm or more, more preferably 250 nm or more, further preferably 350 nm or more, particularly preferably 500 nm or more, preferably 10 μm or less, and more preferably 5 μm or less. When the height of the solder particles is above the lower limit and below the upper limit, the aggregation of the conductive particles can be further effectively suppressed. When the height of the solder particles is above the lower limit and below the upper limit, the solder particles can be more easily metal-bonded between the bonding parts of the electrodes, etc., and a conductive characteristic better than physical contact can be obtained, and the bonding strength can be further improved.

[0160] The height of the solder particle is a line connecting the center of the conductive particle and the tip of the solder particle (solder portion). Figure 1 The distance from the outer surface of the first conductive portion to the tip of the solder particle (solder portion) on the dotted line L1 indicated by , assuming that no solder particle (solder portion) exists. Figure 1 , represents the distance from the intersection L2 of the dotted line L1 and the outer surface of the first conductive portion to the tip of the solder particle (solder portion). The height of the solder particle is preferably the average height of the solder particles in one conductive particle. The height of the solder particle is preferably the average height of the solder particles at 5 locations in the conductive particle.

[0161] The height of the solder particles can be measured, for example, in the following manner.

[0162] In such a way that the content of conductive particles is 30% by weight, it is added to "TECHNOVIT4000" manufactured by Kulzer and dispersed to prepare an embedded resin body for conductive particle inspection. An ion milling device (HITACHI HIGH-TECHNOLOGIES "IM4000") is used to cut out the cross section of the conductive particles by dispersing them near the center of the conductive particles in the embedded resin body for inspection. In addition, a field emission scanning electron microscope (FE-SEM) is used to randomly select conductive particles and observe the solder particles in the conductive particles. The height of the solder particles at 5 positions in the conductive particles is measured, and they are arithmetic averaged and set as the height of the solder particles.

[0163] The aspect ratio of the solder particles is preferably 0.05 or more, more preferably 0.47 or more, further preferably 0.5 or more, preferably 5 or less, and more preferably 3 or less. When the aspect ratio of the solder particles is above the lower limit and below the upper limit, the aggregation of the conductive particles can be further effectively suppressed. When the aspect ratio of the solder particles is above the lower limit and below the upper limit, the solder particles can be more easily metal-bonded between the bonding parts of the electrodes, etc., and the area between the bonding parts of the solder particles and the electrodes, etc. can be sufficiently ensured.

[0164] The aspect ratio of the solder particle is the ratio of the height of the solder particle to the width of the solder particle (height of the solder particle / width of the solder particle), and is calculated based on the height of the solder particle and the width of the solder particle. The height of the solder particle, as described above, is represented by the line ( Figure 1 The distance from the outer surface of the first conductive portion to the tip of the solder particle (solder portion) on the dotted line L1 represented by , assuming that there is no solder particle (solder portion). In addition, the width of the solder particle represents the maximum value of the distance between two points of the periphery of the solder particle (solder portion) connected by a straight line in a direction perpendicular to the line connecting the center of the conductive particle and the tip of the solder particle (solder portion). The width of the solder particle is preferably the average of the widths of the solder particles in one conductive particle. The width of the solder particle is preferably the average of the widths of the solder particles at 5 positions in the conductive particle.

[0165] The width of the solder particles can be measured, for example, in the following manner.

[0166] In such a way that the content of conductive particles is 30% by weight, it is added to "TECHNOVIT4000" manufactured by Kulzer and dispersed to prepare an embedded resin body for conductive particle inspection. An ion milling device (HITACHI HIGH-TECHNOLOGIES "IM4000") is used to cut out the cross section of the conductive particles by dispersing them near the center of the conductive particles in the embedded resin body for inspection. In addition, a field emission scanning electron microscope (FE-SEM) is used to randomly select conductive particles and observe the solder particles in the conductive particles. The width of the solder particles at 5 positions in the conductive particles is measured, and they are arithmetic averaged and set as the width of the solder particles.

[0167] The width of the solder particles is preferably 250 nm or more, more preferably 500 nm or more, further preferably 650 nm or more, preferably 3000 nm or less, more preferably 1700 nm or less, and further preferably 1500 nm or less. When the width of the solder particles is above the lower limit and below the upper limit, the aggregation of the conductive particles can be further effectively suppressed. When the width of the solder particles is above the lower limit and below the upper limit, the solder particles can be more easily metal-bonded between the bonding parts of the electrodes, etc., and a conductive characteristic better than physical contact can be obtained, and the bonding strength can be further improved.

[0168] The method for forming the solder particles is not particularly limited. Examples of the method for forming the solder particles include a method based on electroless plating and a method based on electroplating. It should be noted that the shape formed in the present invention is not only a film shape, but also a granular shape is considered as plating.

[0169] The conductive particles preferably have a metal colloid precipitate or a metal film on the outer surface of the solder particle. The conductive particles may have a metal colloid precipitate or a metal film on the outer surface of the solder particle.

[0170] When the conductive particles satisfy the preferred embodiment, the melting point or metal diffusion temperature of the solder particles (the solder portion) and the conductive portion can be changed to a temperature more suitable for the joining portion of the electrode, etc. As a result, the solder particles can be more easily metal-bonded between the joining portions of the electrode, etc.

[0171] The area of ​​the portion having the metal colloid precipitate or the metal film (the coverage of the metal colloid precipitate or the metal film) is preferably 5% or more, more preferably 40% or more, preferably 100% or less, and more preferably 95% or less out of the total surface area 100% of the solder particles. When the coverage (the coverage of the metal colloid precipitate or the metal film) is above the lower limit and below the upper limit, the melting point or metal diffusion temperature of the solder particles (the solder portion) and the conductive portion can be changed, and can be set to a temperature more suitable for the joining portion of the electrode or the like. As a result, the solder particles can be made to form a metal bond more easily between the joining portions of the electrode or the like.

[0172] The area of ​​the portion having the metal colloid precipitate or the metal film out of 100% of the total surface area of ​​the solder particles (coverage of the metal colloid precipitate or the metal film) can be calculated by performing SEM-EDX analysis and element mapping on the cross section of the solder particles in the conductive particles and performing image analysis.

[0173] The metal type of the metal colloid precipitate or the metal type of the metal film is preferably nickel, cobalt, lead, gold, zinc, palladium, copper, silver, bismuth or indium, and more preferably copper, silver, bismuth or indium. When the metal type of the metal colloid precipitate or the metal type of the metal film satisfies the preferred embodiment, the melting point or metal diffusion temperature of the solder particles (the solder portion) and the conductive portion can be changed to a temperature more suitable for the joining portion of the electrode or the like. As a result, the solder particles can be made to form a metal bond more easily between the joining portions of the electrode or the like.

[0174] The metal colloid used to obtain the metal colloid precipitate is preferably nickel colloid, cobalt colloid, lead colloid, gold colloid, zinc colloid, palladium colloid, copper colloid, silver colloid, bismuth colloid or indium colloid. The metal colloid used to obtain the metal colloid precipitate is more preferably copper colloid, silver colloid, bismuth colloid or indium colloid. The metal film is preferably a nickel film, a cobalt film, a lead film, a gold film, a zinc film, a palladium film, a copper film, a silver film, a bismuth film or an indium film. The metal film is more preferably a copper film, a silver film, a bismuth film or an indium film. When the metal colloid precipitate or the metal film satisfies the preferred embodiment, the melting point or metal diffusion temperature of the solder particles (the solder portion) and the conductive portion can be changed, and can be set to a temperature more suitable for the joining portion of the electrode, etc. As a result, the solder particles can be further easily formed into a metal bond between the joining portions of the electrode, etc.

[0175] The metal colloid precipitate is preferably metal particles. The particle size of the metal particles is preferably greater than 1 nm, more preferably greater than 10 nm, preferably less than 1 μm, and more preferably less than 0.5 μm. The thickness of the metal film is preferably greater than 1 nm, more preferably greater than 10 nm, preferably less than 1 μm, and more preferably less than 0.5 μm. When the particle size of the metal particles or the thickness of the metal film satisfies the preferred embodiment, the melting point or metal diffusion temperature of the solder particles (the solder portion) and the conductive portion can be changed, and can be set to a temperature more suitable for the joining portion of the electrode, etc. As a result, the solder particles can be made to further easily form a metal bond between the joining portions of the electrode, etc.

[0176] The particle size of the metal colloid precipitate or the thickness of the metal film can be measured, for example, in the following manner.

[0177] In such a way that the content of conductive particles is 30% by weight, it is added to "TECHNOVIT4000" manufactured by Kulzer and dispersed to prepare an embedded resin body for conductive particle inspection. An ion milling device (HITACHI HIGH-TECHNOLOGIES "IM4000") is used to cut out the cross section of the conductive particles by dispersing them near the center of the conductive particles in the embedded resin body for inspection. In addition, a field emission scanning electron microscope (FE-SEM) is used to randomly select conductive particles to observe the metal colloid precipitates or metal films in the solder particles. The particle size of the metal colloid precipitate or the thickness of the metal film at 5 positions in the solder particles is measured, and they are arithmetic averaged and set as the particle size of the metal colloid precipitate or the thickness of the metal film.

[0178] The method for configuring the metal colloid precipitate or the metal film on the outer surface of the solder particle is not particularly limited. Examples of the method for configuring the metal colloid precipitate or the metal film on the outer surface of the solder particle include a method based on electroless plating, a method based on electroplating, a method based on physical impact, and a method based on physical vapor deposition or physical adsorption.

[0179] (Core material)

[0180] The conductive particles preferably have protrusions on the outer surface of the conductive portion. The conductive particles preferably have protrusions on the conductive surface. The protrusions are preferably multiple. An oxide film is usually formed on the surface of the electrode in contact with the conductive particles. In the case of using conductive particles having protrusions on the surface of the conductive portion, the oxide film can be effectively removed by pressing the conductive particles and the electrode. Therefore, the electrode and the conductive portion can be further reliably contacted, the contact area between the conductive particles and the electrode can be fully increased, and the connection resistance can be further effectively reduced. In addition, in the case of dispersing the conductive particles in an adhesive and using them as a conductive material, the adhesive between the conductive particles and the electrode can be further effectively removed by the protrusions of the conductive particles. Therefore, the contact area between the conductive particles and the electrode can be fully increased, and the connection resistance can be further effectively reduced.

[0181] The protrusions are different from the solder particles and are used to remove oxide films present on the surfaces of the conductive particles or electrodes or to remove a binder between the conductive particles and the electrodes.

[0182] As a method for forming the protrusion, there can be cited: a method of forming a conductive portion by electroless plating after attaching a core material to the surface of a substrate particle; and a method of forming a conductive portion by electroless plating on the surface of a substrate particle, attaching a core material, and further forming a conductive portion by electroless plating, etc. In addition, the protrusion may be formed without using the core material.

[0183] As other methods for forming the protrusions, there can be cited a method of adding a core material during the stage of forming the conductive portion on the surface of the substrate particles, etc. In addition, it is also possible to use a method of not using the core material to form the protrusions, but forming the conductive portion on the substrate particles by electroless plating, and then precipitating the plating material on the surface of the conductive portion in the form of a protrusion, and further forming the conductive portion by electroless plating, etc.

[0184] As a method for attaching the core material to the surface of the substrate particles, there can be cited: adding the core material to the dispersion of the substrate particles, aggregating the core material and attaching it to the surface of the substrate particles by van der Waals force; and adding the core material to a container filled with substrate particles, a method for attaching the core material to the surface of the substrate particles by mechanical action based on the rotation of the container, etc. From the viewpoint of controlling the amount of the attached core material, the method for attaching the core material to the surface of the substrate particles is preferably: a method for aggregating the core material and attaching it to the surface of the substrate particles in the dispersion.

[0185] As the material constituting the core material, conductive materials and non-conductive materials can be cited. As the conductive material, conductive non-metals such as metals, metal oxides, graphite, and conductive polymers can be cited. As the conductive polymer, polyacetylene can be cited. As the non-conductive material, silicon dioxide, aluminum oxide, zirconium oxide, etc. can be cited. From the viewpoint of further effectively removing the oxide film, the core material is preferably harder. From the viewpoint of further effectively reducing the connection resistance between electrodes, the core material is preferably a metal.

[0186] The metal is not particularly limited. As the metal, metals such as gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium and cadmium, and alloys consisting of two or more metals such as tin-lead alloy, tin-copper alloy, tin-silver alloy, tin-lead-silver alloy and tungsten carbide can be cited. From the viewpoint of further effectively reducing the connection resistance between electrodes, the metal is preferably nickel, copper, silver or gold. The metal may be the same as or different from the metal constituting the conductive portion (conductive layer).

[0187] The shape of the core material is not particularly limited. The shape of the core material is preferably a block. Examples of the core material include a particle-shaped block, an aggregated block formed by agglomeration of a plurality of fine particles, and an indefinite block.

[0188] The particle size of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, preferably 0.9 μm or less, more preferably 0.2 μm or less. When the particle size of the core material is above the lower limit and below the upper limit, the connection resistance between electrodes can be further effectively reduced.

[0189] The particle size of the core material is preferably an average particle size, more preferably a number average particle size. The particle size of the core material can be obtained by observing any 50 core materials through an electron microscope or an optical microscope, and calculating the average value of the particle size of each core material; or using a particle size distribution measuring device. In the observation using an electron microscope or an optical microscope, the particle size of each core material is obtained as a particle size based on an equivalent circle diameter. In the observation using an electron microscope or an optical microscope, the average particle size based on an equivalent circle diameter of any 50 core materials is approximately equal to the average particle size based on an equivalent spherical diameter. In the case of a particle size distribution measuring device, the particle size of each core material is obtained as a particle size based on an equivalent spherical diameter. The average particle size of the core material is preferably calculated using a particle size distribution measuring device.

[0190] The number of the protrusions per one of the conductive particles is preferably 3 or more, more preferably 5 or more. The upper limit of the number of the protrusions is not particularly limited. The upper limit of the number of the protrusions can be appropriately selected in consideration of the particle size of the conductive particles, etc. When the number of the protrusions is greater than the lower limit, the connection resistance between the electrodes can be further effectively reduced.

[0191] The number of protrusions can be counted by observing any conductive particles with an electron microscope or an optical microscope. The number of protrusions is preferably obtained by observing any 50 conductive particles with an electron microscope or an optical microscope and calculating the average number of protrusions in each conductive particle.

[0192] The height of the protrusion is preferably 0.001 μm or more, more preferably 0.05 μm or more, preferably 0.9 μm or less, more preferably 0.2 μm or less. When the height of the protrusion is greater than the lower limit and less than the upper limit, the connection resistance between electrodes can be further effectively reduced.

[0193] The height of the protrusion can be observed and calculated by an electron microscope or an optical microscope. As for the height of the protrusion, it is preferred to calculate the average value of the height of all protrusions of each conductive particle as the height of the protrusion of one conductive particle. The height of the protrusion is preferably obtained by calculating the average value of the height of the protrusion of each conductive particle for any 50 conductive particles.

[0194] (Insulating material)

[0195] The conductive particles preferably have an insulating substance disposed on the outer surface of the conductive portion. In this case, when the conductive particles are used in the connection between electrodes, short circuits between adjacent electrodes can be further effectively prevented. Specifically, when a plurality of conductive particles are in contact, an insulating substance is present between the plurality of electrodes, so that short circuits can be prevented not only between upper and lower electrodes but also between electrodes adjacent in the lateral direction. It should be noted that when connecting between electrodes, by pressurizing the conductive particles with two electrodes, the insulating substance between the conductive portion of the conductive particles and the electrode can be easily removed. In addition, in the case of conductive particles having protrusions on the outer surface of the conductive portion, the insulating substance between the conductive portion of the conductive particles and the electrode can be further easily removed.

[0196] The insulating substance is preferably insulating particles from the viewpoint of being able to more easily remove the insulating substance during compression bonding between electrodes.

[0197] Examples of the material of the insulating substance include the organic material, the inorganic material, and the inorganic substances listed as the material of the substrate particles. The material of the insulating substance is preferably the organic material.

[0198] Other materials of the insulating substance include polyolefin compounds, (meth)acrylate polymers, (meth)acrylate copolymers, block polymers, thermoplastic resins, crosslinked products of thermoplastic resins, thermosetting resins, and water-soluble resins. The insulating substance may be made of one material or two or more materials may be used in combination.

[0199] As the polyolefin compound, polyethylene, ethylene-vinyl acetate copolymer and ethylene-acrylate copolymer can be mentioned. As the (meth)acrylate polymer, polymethyl (meth)acrylate, poly (meth)acrylate dodecyl ester and poly (meth)acrylate stearyl can be mentioned. As the block polymer, polystyrene, styrene-acrylate copolymer, SB type styrene-butadiene block copolymer and SBS type styrene-butadiene block copolymer, and hydrogenated products of these can be mentioned. As the thermoplastic resin, vinyl polymer and vinyl copolymer can be mentioned. As the thermosetting resin, epoxy resin, phenolic resin and melamine resin can be mentioned. As the crosslinked product of the thermoplastic resin, the introduction of polyethylene glycol methacrylate, alkoxylated trimethylolpropane methacrylate, alkoxylated pentaerythritol methacrylate can be mentioned. As the water-soluble resin, polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyvinyl pyrrolidone, polyethylene oxide and methylcellulose can be mentioned. Furthermore, a chain transfer agent may be used to adjust the degree of polymerization. Examples of the chain transfer agent include mercaptans and carbon tetrachloride.

[0200] As the method for configuring the insulating substance on the surface of the conductive part, chemical methods and physical or mechanical methods can be cited. As the chemical method, interfacial polymerization, suspension polymerization in the presence of particles and emulsion polymerization can be cited. As the physical or mechanical method, methods based on spray drying, hybridization, electrostatic adhesion, spraying, immersion and vacuum evaporation can be cited. In the case where electrical connection is achieved between electrodes, from the viewpoint of further effectively improving insulation reliability and conduction reliability, the method for configuring the insulating substance on the surface of the conductive part is preferably a physical method.

[0201] The outer surface of the conductive part and the outer surface of the insulating substance may be coated with a compound having a reactive functional group, respectively. The outer surface of the conductive part and the outer surface of the insulating substance may not be directly chemically bonded, but may be indirectly chemically bonded through a compound having a reactive functional group. After a carboxyl group is introduced into the outer surface of the conductive part, the carboxyl group may be chemically bonded to the functional group on the outer surface of the insulating substance via a polymer electrolyte such as polyethyleneimine.

[0202] In the case where the insulating material is an insulating particle, the particle size of the insulating particle can be appropriately selected according to the particle size of the conductive particle and the purpose of the conductive particle. The particle size of the insulating particle is preferably 10 nm or more, more preferably 100 nm or more, further preferably 300 nm or more, particularly preferably 500 nm or more, preferably 4000 nm or less, more preferably 2000 nm or less, further preferably 1500 nm or less, and particularly preferably 1000 nm or less. When the particle size of the insulating particle is above the lower limit, when the conductive particle is dispersed in the adhesive, the conductive parts of the plurality of conductive particles are not easy to contact each other. When the particle size of the insulating particle is below the upper limit, when the electrodes are connected, it is not necessary to excessively increase the pressure to remove the insulating particles between the electrode and the conductive particle, nor is it necessary to heat at a high temperature to remove the insulating particles between the electrode and the conductive particle.

[0203] The particle size of the insulating particles is preferably an average particle size, preferably a number average particle size. The particle size of the insulating particles can be obtained by observing any 50 insulating particles by an electron microscope or an optical microscope, and calculating the average value of the particle size of each insulating particle; or using a particle size distribution measuring device. In the observation using an electron microscope or an optical microscope, the particle size of each insulating particle is obtained as a particle size based on an equivalent circle diameter. In the observation using an electron microscope or an optical microscope, the average particle size based on an equivalent circle diameter of any 50 insulating particles is approximately equal to the average particle size based on an equivalent spherical diameter. In the case of a particle size distribution measuring device, the particle size of each insulating particle is obtained as a particle size based on an equivalent spherical diameter. The average particle size of the insulating particles is preferably calculated using a particle size distribution measuring device. In the conductive particles, when the particle size of the insulating particles is measured, for example, it can be measured in the following manner.

[0204] The conductive particles were added to "TECHNOVIT4000" manufactured by Kulzer Company and dispersed in such a manner that the content of the conductive particles was 30% by weight to prepare an embedded resin body for conductive particle inspection. An ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES) was used to cut out the cross-section of the conductive particles near the center of the conductive particles dispersed in the embedded resin body for inspection. In addition, 50 conductive particles were randomly selected using a field emission scanning electron microscope (FE-SEM) to observe the insulating particles of each conductive particle. The particle size of the insulating particles in each conductive particle was measured, and they were arithmetic averaged and set as the particle size of the insulating particles.

[0205] (Conductive materials)

[0206] The conductive material of the present invention comprises conductive particles and an adhesive. The conductive particles are the above-mentioned conductive particles. The conductive particles are preferably dispersed in an adhesive for use, and are preferably dispersed in an adhesive for use as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material is preferably used for electrical connection between electrodes. The conductive material is preferably a conductive material for circuit connection. In the conductive material, the conductive particles are used, so that the connection resistance between electrodes can be further effectively reduced, and the aggregation of conductive particles can be further effectively suppressed. In the conductive material, the conductive particles are used, so when the electrodes are electrically connected, the conduction reliability can be further effectively improved, and the insulation reliability can be further effectively improved.

[0207] The adhesive is not particularly limited. As the adhesive, known insulating resins and solvents can be used. The adhesive preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. As the curable component, photocurable components and thermosetting components can be cited. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent.

[0208] Examples of the binder include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, elastomers, and solvents. The binder may be used alone or in combination of two or more.

[0209] As the vinyl resin, vinyl acetate resin, acrylic resin and styrene resin can be mentioned. As the thermoplastic resin, polyolefin resin, ethylene-vinyl acetate copolymer and polyamide resin can be mentioned. As the curable resin, epoxy resin, polyurethane resin, polyimide resin and unsaturated polyester resin can be mentioned. It should be noted that the curable resin can be a room temperature curing resin, a heat curing resin, a light curing resin or a moisture curing resin. The curable resin can be used in combination with a curing agent. As the thermoplastic block copolymer, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer and hydrogenated product of styrene-isoprene-styrene block copolymer can be mentioned. As the elastomer, styrene-butadiene copolymer rubber and acrylonitrile-styrene block copolymer rubber can be mentioned.

[0210] As the solvent, water and organic solvents can be mentioned. From the viewpoint of easy removal, organic solvents are preferred. As the organic solvent, alcohol compounds such as ethanol, ketone compounds such as acetone, methyl ethyl ketone, and cyclohexanone, aromatic hydrocarbon compounds such as toluene, xylene, and tetramethylbenzene, cellosolves, methyl cellosolves, butyl cellosolves, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, tripropylene glycol monomethyl ether and other glycol ether compounds, ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, ester compounds such as propylene carbonate, aliphatic hydrocarbon compounds such as octane and decane, and petroleum solvents such as petroleum ether and naphtha can be mentioned.

[0211] The conductive material may include, in addition to the conductive particles and the binder, various additives such as fillers, extenders, softeners, plasticizers, polymerization catalysts, curing catalysts, colorants, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, antistatic agents, and flame retardants.

[0212] The method for dispersing the conductive particles in the adhesive may use a conventionally known dispersion method, and is not particularly limited. As the method for dispersing the conductive particles in the adhesive, the following methods may be cited. A method in which the conductive particles are added to the adhesive, and then kneaded and dispersed by a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer, and then added to the adhesive, and then kneaded and dispersed by a planetary mixer or the like. A method in which the conductive particles are diluted with water or an organic solvent, and then added to the adhesive, and then kneaded and dispersed by a planetary mixer or the like.

[0213] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, preferably 400 Pa·s or less, and more preferably 300 Pa·s or less. When the viscosity of the conductive material at 25°C is above the lower limit and below the upper limit, the connection resistance between the electrodes can be further effectively reduced, and the connection reliability between the electrodes can be further effectively improved. The viscosity (η25) can be appropriately adjusted by the type and amount of the mixed components.

[0214] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) under the conditions of 25° C. and 5 rpm.

[0215] The conductive material of the present invention can be used as a conductive paste and a conductive film. When the conductive material of the present invention is a conductive film, a film not containing conductive particles can be laminated on the conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.

[0216] In 100 wt % of the conductive material, the content of the binder is preferably 10 wt % or more, more preferably 30 wt % or more, further preferably 50 wt % or more, particularly preferably 70 wt % or more, preferably 99.99 wt % or less, more preferably 99.9 wt % or less. When the content of the binder is above the lower limit and below the upper limit, the connection resistance between the electrodes can be further effectively reduced, and the connection reliability between the electrodes can be further effectively improved.

[0217] In 100 wt % of the conductive material, the content of the conductive particles is preferably 0.01 wt % or more, more preferably 0.1 wt % or more, preferably 80 wt % or less, more preferably 60 wt % or less, further preferably 40 wt % or less, particularly preferably 20 wt % or less, and most preferably 10 wt % or less. When the content of the conductive particles is above the lower limit and below the upper limit, the connection resistance between the electrodes can be further effectively reduced, and the connection reliability between the electrodes can be further effectively improved.

[0218] Flux:

[0219] The conductive material may include a soldering flux. By using the soldering flux, when the electrodes are electrically connected, the conduction reliability can be further effectively improved. The soldering flux is not particularly limited. As the soldering flux, a soldering flux commonly used in solder bonding or the like can be used.

[0220] Examples of the soldering flux include zinc chloride, a mixture of zinc chloride and an inorganic halogen compound, a mixture of zinc chloride and an inorganic acid, a molten salt, phosphoric acid, a derivative of phosphoric acid, an organic halogen compound, hydrazine, an amine compound, an organic acid, and rosin. The soldering flux may be used alone or in combination of two or more.

[0221] As the molten salt, ammonium chloride and the like can be cited. As the organic acid, lactic acid, citric acid, stearic acid, glutamic acid and glutaric acid and the like can be cited. As the rosin, activated rosin and inactivated rosin and the like can be cited. The soldering flux is preferably an organic acid or rosin having two or more carboxyl groups. The soldering flux can be an organic acid or rosin having two or more carboxyl groups. By using an organic acid or rosin having two or more carboxyl groups, the conduction reliability between the electrodes is further improved.

[0222] Examples of the organic acid having two or more carboxyl groups include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid.

[0223] Examples of the amine compound include cyclohexylamine, dicyclohexylamine, benzylamine, dibenzhydrylamine, imidazole, benzimidazole, phenylimidazole, carboxybenzimidazole, benzotriazole, and carboxybenzotriazole.

[0224] The rosin is a rosin with abietic acid as the main component. Examples of the rosin include abietic acid and acrylic acid-modified rosin. The soldering flux is preferably a rosin, more preferably abietic acid. By using the preferred soldering flux, the conduction reliability between the electrodes is further improved.

[0225] The active temperature (melting point) of the soldering flux is preferably 50°C or more, more preferably 70°C or more, further preferably 80°C or more, and preferably 200°C or less, more preferably 190°C or less, further preferably 160°C or less, further preferably 150°C or less, and further preferably 140°C or less. When the active temperature of the soldering flux is above the lower limit and below the upper limit, the soldering flux effect is further effectively exerted, and the conduction reliability between electrodes can be further effectively improved. The active temperature (melting point) of the soldering flux is preferably 80°C or more and 190°C or less. The active temperature (melting point) of the soldering flux is particularly preferably 80°C or more and 140°C or less.

[0226] Examples of the soldering flux having an active temperature (melting point) of 80°C to 190°C include dicarboxylic acids such as succinic acid (melting point 186°C), glutaric acid (melting point 96°C), adipic acid (melting point 152°C), pimelic acid (melting point 104°C), suberic acid (melting point 142°C), benzoic acid (melting point 122°C), malic acid (melting point 130°C), etc.

[0227] Furthermore, the boiling point of the soldering flux is preferably 200° C. or lower.

[0228] The soldering flux may be dispersed in the conductive material or may be attached to the surface of the conductive particles. When the electrodes are electrically connected, the soldering flux is preferably attached to the surface of the conductive particles from the viewpoint of further effectively improving the conduction reliability.

[0229] From the viewpoint of further effectively improving conduction reliability, the soldering flux is preferably a salt of an acid compound and a base compound.

[0230] The acid compound is preferably an organic compound having a carboxyl group. Examples of the acid compound include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, citric acid, and malic acid as aliphatic carboxylic acids, cyclohexane acid and 1,4-cyclohexane dicarboxylic acid as cyclic aliphatic carboxylic acids, and isophthalic acid, terephthalic acid, trimellitic acid, and ethylenediaminetetraacetic acid as aromatic carboxylic acids. From the viewpoint of further effectively improving conduction reliability, the acid compound is preferably glutaric acid, cyclohexane acid, or adipic acid.

[0231] The base compound is preferably an organic compound having an amino group. Examples of the base compound include diethanolamine, triethanolamine, methyldiethanolamine, ethyldiethanolamine, cyclohexylamine, dicyclohexylamine, benzylamine, dibenzhydrylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-tert-butylbenzylamine, N-methylbenzylamine, N-ethylbenzylamine, N-phenylbenzylamine, N-tert-butylbenzylamine, N-isopropylbenzylamine, N,N-dimethylbenzylamine, imidazole compounds, and triazole compounds. From the viewpoint of further effectively improving conduction reliability, the base compound is preferably benzylamine.

[0232] The content of the soldering flux in 100 wt % of the conductive material is preferably 0.5 wt % or more, preferably 30 wt % or less, and more preferably 25 wt % or less. When the content of the soldering flux is above the lower limit and below the upper limit, it is possible to make it more difficult for an oxide film to form on the surface of the electrode, and the oxide film formed on the surface of the electrode can be further effectively removed.

[0233] (Connection structure)

[0234] The connection structure of the present invention comprises: a first connection object part having a first electrode on the surface, a second connection object part having a second electrode on the surface, and a connection portion connecting the first connection object part and the second connection object part. In the connection structure of the present invention, the connection portion is formed by conductive particles, or is formed by a conductive material containing the conductive particles and a binder. In the connection structure of the present invention, the conductive particles are the above-mentioned conductive particles. In the connection structure of the present invention, the first electrode and the second electrode are electrically connected through the conductive particles.

[0235] Fig. 9 It is a front cross-sectional view schematically showing a connection structure using conductive particles according to a fourth embodiment of the present invention.

[0236] Fig. 9 The connection structure 81 shown in FIG. 1 includes a first connection object member 82, a second connection object member 83, and a connection portion 84 connecting the first connection object member 82 and the second connection object member 83. The connection portion 84 is formed of a conductive material containing conductive particles 21. Fig. 9 In FIG. 1 , for the convenience of illustration, the conductive particles 21 are schematically shown.

[0237] The first connection object member 82 has a plurality of first electrodes 82a on the surface (upper surface). The second connection object member 83 has a plurality of second electrodes 83a on the surface (lower surface). The first electrode 82a and the second electrode 83a are electrically connected via one or more conductive particles 21. Therefore, the first connection object member 82 and the second connection object member 83 are electrically connected via the conductive particles 21.

[0238] The method for manufacturing the connection structure is not particularly limited. As an example of the method for manufacturing the connection structure, there can be cited a method in which the conductive material is arranged between the first connection object part and the second connection object part, and after obtaining a laminate, the laminate is heated and pressurized. By heating and pressurizing, the conductive part (solder part) of the conductive particles 21 is melted, and the electrodes are electrically connected through the conductive particles 21. In addition, when the adhesive contains a thermosetting compound, the thermosetting compound is thermally cured to form the connection part that connects the first connection object part and the second connection object part through a thermally cured solid. The pressure of the pressurization is 9.8×10 4 Pa~4.9×10 6 The heating temperature is 120°C to 220°C.

[0239] Fig.10 is enlarged and schematically represented Fig. 92 is a front cross-sectional view of a connection portion between conductive particles and an electrode in a connection structure shown in FIG.

[0240] like Fig.10 As shown in FIG. 1 , in the connection structure 81, after the second conductive part (solder part) 22B of the conductive particle 21 is melted by heating and pressurizing the laminate, the melted second conductive part (solder part) part 22Ba is in full contact with the first electrode 82a and the second electrode 83a. That is, by using the conductive particle 21 whose surface layer is a metal such as nickel, gold or copper, the contact area between the conductive particle 21 and the first electrode 82a and the second electrode 83a is increased compared with the case where the conductive particle 21 whose surface layer is a solder part is used. Therefore, the conduction reliability of the connection structure 81 is improved.

[0241] The first connection object component and the second connection object component are not particularly limited. Specifically, the first connection object component and the second connection object component include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, and electronic components such as circuit substrates such as resin films, printed substrates, flexible printed substrates, flexible flat cables, rigid flexible substrates, glass epoxy substrates, and glass substrates. The first connection object component and the second connection object component are preferably electronic components.

[0242] As the electrode provided on the connection object part, metal electrodes such as gold electrode, nickel electrode, tin electrode, aluminum electrode, copper electrode, molybdenum electrode, silver electrode, SUS electrode and tungsten electrode can be cited. When the connection object part is a flexible printed circuit board, the electrode is preferably a gold electrode, a nickel electrode, a tin electrode, a silver electrode or a copper electrode. When the connection object part is a glass substrate, the electrode is preferably an aluminum electrode, a copper electrode, a molybdenum electrode, a silver electrode or a tungsten electrode. It should be noted that when the electrode is an aluminum electrode, it can be an electrode formed only of aluminum, or it can be an electrode formed by laminating an aluminum layer on the surface of a metal oxide layer. As the material of the metal oxide layer, indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element can be cited. As the trivalent metal element, Sn, Al and Ga can be cited.

[0243] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples. The present invention is not limited to the following Examples.

[0244] (Example 1)

[0245] Preparation of conductive particles 1:

[0246] As substrate particles (S1), divinylbenzene copolymer resin particles ("MICROPEARL SP-220" manufactured by Sekisui Chemical Co., Ltd., particle size 20 μm) were prepared.

[0247] After dispersing 10 parts by weight of the substrate particles (S1) into 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution by an ultrasonic disperser, the solution is filtered to remove the substrate particles (S1). Next, the substrate particles (S1) are added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surface of the substrate particles (S1). After the activated substrate particles (S1) are fully washed with water, they are added to 500 parts by weight of distilled water and dispersed to obtain a suspension (A1).

[0248] The suspension (A1) was added to a solution containing 25 g / L of nickel sulfate, 15 ppm of thallium nitrate, and 10 ppm of bismuth nitrate to obtain a particle mixed solution (B1).

[0249] Furthermore, a nickel plating solution (C1) (pH 5.5) containing 100 g / L of nickel sulfate, 40 g / L of sodium hypophosphite, 15 g / L of sodium citrate, 25 ppm of thallium nitrate, and 10 ppm of bismuth nitrate was prepared.

[0250] Furthermore, as an electroless tin plating solution for forming solder particles, a tin plating solution (D1) was prepared in which a mixed solution containing 15 g / L of tin sulfate, 45 g / L of ethylenediaminetetraacetic acid, and 1.5 g / L of phosphinic acid was adjusted to pH 8.5 with sodium hydroxide.

[0251] Furthermore, as a reducing solution, a reducing solution (E1) was prepared in which a solution containing 5 g / L of sodium borohydride was adjusted to pH 10.0 with sodium hydroxide.

[0252] The nickel plating solution (C1) was slowly added dropwise to the particle mixture (B1) at 50°C in which the particles were dispersed, and electroless nickel plating was performed. The nickel plating solution (C1) was added at a dropping speed of 12.5 mL / min, and the dropping time was 30 minutes, and electroless nickel plating (Ni plating step) was performed. Thus, a particle mixture (F1) containing particles having a nickel-phosphorus alloy conductive portion as the first conductive portion on the surface of the substrate particle S1 was obtained.

[0253] Then, the particle mixture (F1) was filtered to remove the particles, and washed with water to obtain particles having a nickel-phosphorus alloy conductive portion disposed on the surface of the substrate particles S1. The particles were fully washed with water, added to 500 parts by weight of distilled water, and dispersed to obtain a particle mixture (G1).

[0254] Next, the tin plating solution (D1) is slowly added to the 60°C particle mixture (G1) in which the particles are dispersed. Then, the reducing solution (E1) is added dropwise to perform electroless tin plating. The dropping speed of the reducing solution (E1) is 0.5 mL / min, the dropping time is 40 minutes, and then stirred for 10 minutes to perform electroless tin plating. Then, the particles are taken out by filtration, washed with water, and dried to obtain conductive particles 1 having a nickel-phosphorus alloy conductive portion and a tin conductive portion (solder particles) on the surface of the substrate particles S1 (the overall thickness of the conductive portion at the portion without solder particles: 0.1 μm, the height of the solder particles: 0.6 μm).

[0255] (Example 2)

[0256] Preparation of Conductive Particles 2:

[0257] The suspension (A1) of Example 1 was prepared.

[0258] The suspension (A1) was added to a solution containing 2 g / L potassium gold cyanide, 10 g / L sodium citrate, 0.5 g / L ethylenediaminetetraacetic acid, and 5 g / L sodium hydroxide to obtain a particle mixture (B2).

[0259] In addition, as an electroless gold plating solution, a gold plating solution (C2) (pH 8.0) containing 10 g / L potassium gold cyanide, 20 g / L sodium citrate, 5 ppm thallium nitrate, 3.0 g / L ethylenediaminetetraacetic acid, 20 g / L sodium hydroxide and 10 g / L dimethylamine borane was prepared.

[0260] Furthermore, as a tin solution for forming solder particles, the tin plating solution (D1) of Example 1 and a reducing solution (E1) were prepared.

[0261] The gold plating solution (C2) was slowly added to the 60°C particle mixture (B2) in which the particles were dispersed, and electroless gold plating was performed. The drop rate of the gold plating solution (C2) was 2 mL / min, and the drop time was 45 minutes, and electroless gold plating was performed. Thus, a particle mixture (D2) containing particles having a gold metal portion as the first conductive portion arranged on the surface of the substrate particle S1 was obtained.

[0262] Then, the particle mixture (D2) was filtered to remove particles, and washed with water to obtain particles having a gold conductive portion disposed on the surface of the substrate particles S1. The particles were thoroughly washed with water, added to 500 parts by weight of distilled water, and dispersed to obtain a particle mixture (E2).

[0263] Then, solder particles were formed by the same method as in Example 1 using the tin plating solution (D1) and the reducing solution (E1), thereby obtaining a particle mixed solution (F2) containing particles in which solder particles were formed on the gold conductive parts.

[0264] Then, the particles are taken out by filtering the particle mixture (F2), and washed with water to obtain particles having a gold conductive portion and solder particles arranged on the surface of the substrate particles S1. The particles are fully washed with water, added to 500 parts by weight of distilled water, and dispersed to obtain a particle mixture (G2).

[0265] Next, the gold plating solution (C2) is slowly dripped into the 60°C particle mixture (G2) in which the particles are dispersed, and electroless gold plating is performed. The dripping speed of the gold plating solution (C2) is 1 mL / min, and the dripping time is 1 minute, and electroless gold plating is performed. Then, the particles are taken out by filtration, and the conductive particles 2 having a gold thin film (thickness of the metal film: 0.01 μm) on the surface of the substrate particles S1 (thickness of the entire conductive part: 0.1 μm) and the solder particles (height of the solder particles: 0.6 μm) are obtained by washing and drying.

[0266] (Example 3)

[0267] Preparation of conductive particles 3:

[0268] Conductive particles having a nickel-phosphorus alloy conductive portion and solder particles on substrate particles were obtained in the same manner as in Example 1. The obtained conductive particles were added to 500 parts by weight of distilled water and dispersed to obtain a suspension (A3).

[0269] Furthermore, as an electroless silver plating solution, a silver plating solution (B3) was prepared in which a mixed solution of 30 g / L of silver nitrate, 100 g / L of succinimide, and 20 g / L of formaldehyde was adjusted to pH 8.0 with aqueous ammonia.

[0270] Furthermore, the particle mixed solution (C3) was obtained by mixing and dispersing the 60°C suspension solution (A3) in the silver plating solution (B3).

[0271] Next, the silver plating solution (B3) is slowly dripped into the particle mixture (C3) at 60°C in which the particles are dispersed, and electroless silver plating is performed. The dropping speed of the silver plating solution (B3) is 10 mL / min, and the dropping time is 10 minutes, and electroless plating is performed. Then, the particles are taken out by filtration, and the conductive particles 3 having a silver thin film (thickness of the metal film: 0.01 μm) on the surface of the substrate particles S1 are obtained by washing with water and drying.

[0272] (Example 4)

[0273] Preparation of conductive particles 4:

[0274] The suspension (A3) of Example 3 was prepared.

[0275] As a silver solution, a silver solution (B4) was prepared in which a mixed solution containing 1 g / L of silver nitrate, 30 g / L of ethylenediaminetetraacetic acid, and 20 ppm of polyethylene glycol (molecular weight 6000) was adjusted to pH 11 with sodium hydroxide.

[0276] Furthermore, as a reducing solution, a solution containing 10 g / L of sodium borohydride and 40 g / L of sodium hydroxide was prepared as a reducing solution for forming a metal colloidal precipitate (D4).

[0277] Furthermore, the suspension (A3) is mixed and dispersed in the silver solution (B4) to obtain a particle mixed solution (C4).

[0278] Next, 1 part by weight of the reducing solution (D4) for forming the metal colloid precipitate was added to the 25°C particle mixed solution (C4) in which the particles were dispersed, and the mixture was stirred for 10 minutes. The particles were then taken out by filtration, washed with water, and dried to obtain conductive particles 4 having silver colloid precipitates (particle size of the metal colloid precipitates: 0.02 μm) on the surface of the conductive particles.

[0279] (Example 5)

[0280] Preparation of conductive particles 5:

[0281] The suspension (A3) of Example 3 was prepared.

[0282] In addition, as an indium solution, an indium solution (B5) was prepared in which a mixed solution containing 5 g / L of indium chloride, 40 g / L of ethylenediaminetetraacetic acid, and 0.01 g / L of polyvinylpyrrolidone was adjusted to pH 10 with sodium hydroxide.

[0283] Furthermore, as a reducing solution, the reducing solution for forming a colloidal precipitate (D4) of Example 4 was prepared.

[0284] The particle mixture (C5) is obtained by mixing and dispersing the suspension (A3) into the indium solution (B5).

[0285] 10 parts by weight of the reducing solution (D4) for forming the metal colloid precipitate was added to the 50°C particle mixture (C5) in which the particles were dispersed, and the mixture was stirred for 60 minutes. The particles were then taken out by filtration, washed with water, and dried to obtain conductive particles 5 having indium colloid precipitates (particle size of the metal colloid precipitates: 0.01 μm) on the surface of the conductive particles.

[0286] (Example 6)

[0287] Preparation of conductive particles 6:

[0288] The suspension (A3) of Example 3 was prepared.

[0289] In addition, as a copper solution, a copper solution (B6) was prepared in which a mixed solution containing 10 g / L of copper sulfate pentahydrate, 40 g / L of ethylenediaminetetraacetic acid, and 0.1 g / L of polyvinyl pyrrolidone was adjusted to pH 9.0 with sodium hydroxide.

[0290] Furthermore, as a reducing solution, the reducing solution for forming a metal colloid precipitate (D4) of Example 4 was prepared.

[0291] The particle mixed solution (C6) is obtained by mixing and dispersing the suspension (A3) into the copper solution (B6).

[0292] 5 parts by weight of the reducing solution (D4) for forming the metal colloid precipitate was added to the 25°C particle mixed solution (C6) in which the particles were dispersed, and the mixture was stirred for 60 minutes. The particles were then taken out by filtration, washed with water, and dried to obtain conductive particles 6 having copper colloid precipitates (particle size of the metal colloid precipitates: 0.01 μm) on the surface of the conductive particles.

[0293] (Example 7)

[0294] Preparation of conductive particles 7:

[0295] As an electroless tin plating solution for forming solder particles, a tin plating solution (B7) was prepared in which a mixed solution containing 15 g / L of tin sulfate, 45 g / L of ethylenediaminetetraacetic acid, 1.5 g / L of phosphinic acid, and 10 g / L of trehalose dihydrate was adjusted to pH 9.0 with sodium hydroxide.

[0296] Conductive particles 7 (total thickness of the conductive portion without solder particles: 0.2 μm, height of solder particles: 0.9 μm) were obtained in the same manner as in Example 1 except that the electroless tin plating solution for forming solder particles (D1) was changed to the electroless tin plating solution for forming solder particles (B7).

[0297] (Example 8)

[0298] Preparation of conductive particles 8:

[0299] (1) Preparation of polysiloxane oligomers

[0300] Into a 100 ml separable flask set in a warm bath, 1 part by weight of 1,3-divinyltetramethyldisiloxane and 20 parts by weight of a 0.5% by weight aqueous solution of p-toluenesulfonic acid were added. After stirring at 40°C for 1 hour, 0.05 parts by weight of sodium bicarbonate were added. Then, 10 parts by weight of dimethoxymethylphenylsilane, 49 parts by weight of dimethyldimethoxysilane, 0.6 parts by weight of trimethylmethoxysilane and 3.6 parts by weight of methyltrimethoxysilane were added and stirred for 1 hour. Then, 1.9 parts by weight of a 10% by weight aqueous solution of potassium hydroxide were added, the temperature was raised to 85°C and the pressure was reduced by an aspirator, while stirring for 10 hours, and the reaction was carried out. After the reaction was completed, the pressure was returned to normal and cooled to 40°C, 0.2 parts by weight of acetic acid was added, and the mixture was allowed to stand in a separatory funnel for more than 12 hours. The lower layer after the two-layer separation was taken out and purified by an evaporator to obtain a polysiloxane oligomer.

[0301] (2) Preparation of polysiloxane particle materials (including organic polymers)

[0302] A solution A was prepared by dissolving 0.5 parts by weight of tert-butyl peroxy-2-ethylhexanoate (polymerization initiator, "PERBUTYL O" manufactured by NOF) in 30 parts by weight of the obtained polysiloxane oligomer. In addition, 0.8 parts by weight of a 40% by weight aqueous solution of triethanolamine lauryl sulfate (emulsifier) ​​and 80 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol (polymerization degree: about 2000, saponification degree: 86.5 to 89 mol%, "GOHSENOL GH-20" manufactured by Nippon Synthetic Chemical Co., Ltd.) were mixed in 150 parts by weight of ion exchange water to prepare an aqueous solution B. After adding the solution A to a separable flask placed in a warm bath, the aqueous solution B was added. Then, emulsification was performed using a Shirasu Porous Glass (SPG) membrane (average pore diameter of about 1 μm). Then, the temperature was raised to 85° C. and polymerization was performed for 9 hours. All the polymerized particles were washed with water by centrifugation and freeze-dried. After drying, the mixture was pulverized by a ball mill until the aggregate of the particles had a target ratio (average secondary particle size / average primary particle size), thereby obtaining polysiloxane particles (substrate particles S2) having a particle size of 3.0 μm.

[0303] Except having changed the said substrate particle S1 into the said substrate particle S2, it carried out similarly to Example 1, and obtained the electroconductive particle 8.

[0304] (Example 9)

[0305] Preparation of conductive particles 9:

[0306] Polysiloxane particles (substrate particles S3) having a particle size of 3.0 μm were obtained in the same manner as in Example 8 except that a silicone oil having acrylic acid at both ends (“X-22-2445” manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of the polysiloxane oligomer.

[0307] Conductive particles 9 were obtained in the same manner as in Example 1 except that the substrate particles S1 were changed to the substrate particles S3.

[0308] (Example 10)

[0309] Preparation of conductive particles 10:

[0310] The substrate particles S4 were prepared, which were different from the substrate particles S1 only in particle diameter and had a particle diameter of 3.0 μm.

[0311] The conductive particles 10 were obtained in the same manner as in Example 1 except that the substrate particles S1 were changed to the substrate particles S4.

[0312] (Example 11)

[0313] Preparation of conductive particles 11:

[0314] The substrate particles S5 were prepared, which were different from the substrate particles S1 only in particle diameter and had a particle diameter of 10.0 μm.

[0315] The conductive particles 11 were obtained in the same manner as in Example 1 except that the substrate particles S1 were changed to the substrate particles S5.

[0316] (Example 12)

[0317] Preparation of conductive particles 12:

[0318] The substrate particles S6 different from the substrate particles S1 only in particle diameter and having a particle diameter of 35.0 μm were prepared.

[0319] The conductive particles 12 were obtained in the same manner as in Example 1 except that the substrate particles S1 were changed to the substrate particles S6.

[0320] (Example 13)

[0321] Preparation of conductive particles 13:

[0322] The suspension (A1) of Example 1 was prepared.

[0323] A metal nickel slurry (average particle size 150 nm) was prepared, and 1 part by weight of the suspension (A1) was added over 3 minutes to obtain a particle mixture (B13) containing substrate particles S1 to which a core material was attached. Then, electroless nickel plating was performed using the nickel plating solution (C1) in the same manner as in Example 1 to obtain a particle mixture (F13) containing particles having a nickel-phosphorus alloy conductive portion as a first conductive portion on the surface of substrate particles containing a metal nickel core material.

[0324] Then, the particles are taken out by filtering the particle mixture (F13), and washed with water to obtain particles having a nickel-phosphorus alloy conductive portion containing a metal nickel core material disposed on the surface of the substrate particles S1. The particles are fully washed with water, added to 500 parts by weight of distilled water, and dispersed to obtain a particle mixture (G13).

[0325] Then, solder particles were formed using the tin plating solution (D1) and the reducing solution (E1) in the same manner as in Example 1, thereby obtaining a particle mixture solution (H13) containing particles in which solder particles were formed on the nickel-phosphorus alloy conductive portion.

[0326] Then, the particles are taken out by filtration, washed with water, and dried to obtain conductive particles 13 having a nickel-phosphorus alloy conductive part containing a core material (the overall thickness of the conductive part in the part without core material: 0.1 μm) and solder particles (height of solder particles: 0.6 μm) on the surface of the substrate particle S1.

[0327] (Example 14)

[0328] Preparation of conductive particles 14:

[0329] A titanium oxide particle slurry (average particle size: 150 nm) was prepared.

[0330] Conductive particles 14 were obtained in the same manner as in Example 13 except that the metal nickel particle slurry was changed to the titanium oxide particle slurry.

[0331] (Example 15)

[0332] Preparation of conductive particles 15:

[0333] Alumina particle slurry (average particle size 150 nm) was prepared.

[0334] Conductive particles 15 were obtained in the same manner as in Example 13 except that the metal nickel particle slurry was changed to the aluminum oxide particle slurry.

[0335] (Example 16)

[0336] Preparation of conductive particles 16:

[0337] Prepare a 1000mL separable flask equipped with a 4-mouth separable cover, a stirring blade, a three-way stopcock, a cooling tube and a temperature probe. In the separable flask, a monomer composition containing 100mmol of methyl methacrylate, 1mmol of N,N,N-trimethyl-N-2-methacryloyloxyethylammonium chloride, and 1mmol of 2,2'-azobis(2-amidinopropane) dihydrochloride is weighed in ion exchange water so that the solid fraction is 5% by weight. Then, stir at 200rpm and polymerize for 24 hours in a nitrogen atmosphere at 70°C. After the reaction is completed, freeze-dry to obtain insulating particles having ammonium groups on the surface and an average particle size of 220nm and a CV value of 10%.

[0338] The insulating particles were dispersed in ion-exchanged water under ultrasonic irradiation to obtain a 10 wt % aqueous dispersion of the insulating particles.

[0339] 10 g of the conductive particles obtained in Example 1 were dispersed in 500 mL of ion exchange water, 4 g of the aqueous dispersion of insulating particles was added, and stirred at room temperature for 6 hours. The mixture was filtered through a 30 μm mesh filter, washed with methanol, and dried to obtain conductive particles 16 with insulating particles attached thereto.

[0340] When observed by a scanning electron microscope (SEM), only one coating layer composed of insulating particles was formed on the surface of the conductive particles 16. When the coating area of ​​the insulating particles with respect to an area of ​​2.5 μm from the center of the conductive particles 16 (i.e., the projected area of ​​the particle diameter of the insulating particles) was calculated by image analysis, the coverage was 30%.

[0341] (Example 17)

[0342] Preparation of conductive particles 17:

[0343] Except for changing the dropping time of the reducing solution (E1) to 20 minutes, the same method as in Example 1 was used to obtain conductive particles 17 having a nickel-phosphorus alloy conductive portion and a tin conductive portion (solder particles) on the surface of the substrate particles S1 (the overall thickness of the conductive portion at the portion without solder particles: 0.1 μm, the height of the solder particles: 0.3 μm).

[0344] (Comparative Example 1)

[0345] Preparation of conductive particles A:

[0346] In the same manner as in Example 1, a particle mixed solution (G1) was obtained.

[0347] In addition, as an electroless tin plating solution, a tin plating solution (d1) was prepared by adjusting a mixed solution containing 20 g / L of tin chloride, 50 g / L of nitrilotriacetic acid, 2 g / L of thiourea, 1 g / L of thiomalic acid, 7.5 g / L of ethylenediaminetetraacetic acid, and 15 g / L of titanium trichloride to pH 7.0 with sulfuric acid.

[0348] Next, the tin plating solution (d1) is slowly dripped into the 70°C particle mixture (G1) in which the particles are dispersed, and electroless tin plating is performed. The dropping speed of the tin plating solution (d1) is 30 mL / min, and the dropping time is 20 minutes, and electroless tin plating is performed. Then, the particles are taken out by filtration, and the conductive particles A having a nickel-phosphorus alloy conductive part and a tin conductive part (the thickness of the conductive part as a whole: 0.3 μm) on the surface of the substrate particles S1 are obtained by washing with water and drying.

[0349] (Comparative Example 2)

[0350] Preparation of conductive particles B:

[0351] In the same manner as in Example 13, a particle mixed solution (G13) was obtained.

[0352] Furthermore, an electroless tin plating solution (d1) of Comparative Example 1 was prepared.

[0353] Electroless tin plating was performed in the same manner as in Comparative Example 1 to obtain conductive particles B having a nickel-phosphorus alloy conductive portion containing a core substance and a tin conductive portion (the total thickness of the conductive portion in the portion without the core substance: 0.3 μm) on the surface of substrate particle S1.

[0354] (Comparative Example 3)

[0355] Preparation of conductive particles C:

[0356] In the same manner as in Example 1, a particle mixed solution (F1) was obtained.

[0357] Then, the particle mixture (F1) was filtered to take out the particles, and the particles were washed with water and dried to obtain conductive particles C having a nickel-phosphorus alloy conductive portion arranged on the surface of the substrate particles S1 (conductive portion thickness: 0.1 μm).

[0358] (evaluate)

[0359] (1) Metal diffusion state of the conductive part

[0360] The obtained conductive particles were added to and dispersed in "STRUCTBOND XN-5A" manufactured by Mitsui Chemicals, Inc. so as to have a content of 10% by weight, thereby preparing an anisotropic conductive paste.

[0361] A transparent glass substrate having a copper electrode pattern with an L / S of 200 μm / 200 μm on the upper surface was prepared. Also, a semiconductor chip having a gold electrode pattern with an L / S of 200 μm / 200 μm on the lower surface was prepared.

[0362] On the transparent glass substrate, the anisotropic conductive paste just prepared was applied in a manner to a thickness of 30 μm to form an anisotropic conductive paste layer. Next, the semiconductor chip was stacked on the anisotropic conductive paste layer in a manner such that the electrodes were opposite to each other. Then, a pressurized heating head was placed on the upper surface of the semiconductor chip, and the temperature of the head was adjusted so that the temperature of the anisotropic conductive paste layer was 250° C. A pressure of 0.5 MPa was applied to cure the anisotropic conductive paste layer at 250° C., thereby obtaining a connection structure.

[0363] In the obtained connection structure, the connection structure was observed in cross section to determine the metal diffusion state of the conductive portion.

[0364] Using a transmission electron microscope FE-TEM (JEOL Ltd. "JEM-2010FEF"), the contact portions between the conductive particles and the copper electrode pattern and the gold electrode pattern were subjected to element mapping by an energy dispersive X-ray analyzer (EDX) to observe the diffusion state of the conductive portion. The diffusion state of the conductive portion was determined based on the following criteria.

[0365] [Criteria for determining the diffusion state of the conductive portion]

[0366] A: In the connection part, the conductive metal in the conductive particles diffuses to the copper electrode pattern and the gold electrode pattern.

[0367] B: In the connection part, the conductive part in the conductive particles is not metal diffused to the copper electrode pattern and the gold electrode pattern

[0368] (2) Melting deformation state of the conductive part

[0369] Prepare the connection structure obtained in the evaluation of (1). Put the prepared connection structure into "TECHNOVIT4000" manufactured by Kulzer and cure it to prepare an embedding resin body for connection structure inspection. Use an ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES) to cut out the cross section of the conductive particles in a manner near the center of the connection structure in the embedding resin body for inspection.

[0370] Furthermore, the cross section of the obtained connection structure was observed using a scanning electron microscope (FE-SEM) to confirm whether the conductive portion of the conductive particles solidified after melting and deformation. The melting and deformation state of the conductive portion was determined based on the following criteria.

[0371] [Criteria for determining the melt deformation state of the conductive portion]

[0372] A: The conductive part solidifies after melting and deformation

[0373] B: No melting deformation occurs in the conductive part

[0374] (3) Bonding state of conductive parts

[0375] Prepare the connection structure obtained in the evaluation of (1). Put the prepared connection structure into "TECHNOVIT4000" manufactured by Kulzer and cure it to prepare an embedding resin body for connection structure inspection. Use an ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES) to cut out the cross section of the conductive particles in a manner near the center of the connection structure in the embedding resin body for inspection.

[0376] The obtained connection structure was observed in cross section using a scanning electron microscope (FE-SEM) to confirm the bonding state of the conductive portion. The bonding state of the conductive portion was determined based on the following criteria.

[0377] [Criteria for determining the bonding state of the conductive portion]

[0378] A: In the connection part, the conductive part of 5 or more particles out of 10 conductive particles is melted and deformed, then solidified and connected to the electrode.

[0379] B: In the connection part, the conductive part of at least one but less than five of the ten conductive particles melts and deforms and solidifies, thereby achieving bonding with the electrode.

[0380] C: In the connection part, there is no particle with melting deformation in the conductive part among the 10 conductive particles, and the connection with the electrode is achieved only by metal diffusion.

[0381] D: In the connection portion, there is no particle that has achieved bonding among the 10 conductive particles.

[0382] (4) The area of ​​the portion having the solder portion (solder particles) out of 100% of the total surface area of ​​the substrate particles (coverage rate of the solder portion (solder particles))

[0383] For the obtained conductive particles, the area of ​​the portion where the solder portion exists out of 100% of the total surface area of ​​the substrate particles (coverage of the solder portion) is calculated. The coverage (coverage of the solder portion) is calculated by performing SEM-EDX analysis on the cross section of the conductive particles and performing element mapping and image analysis.

[0384] (5) Particle size of conductive particles

[0385] The particle size of the obtained conductive particles was calculated using a particle size distribution analyzer ("Multisizer 4" manufactured by Beckman Coulter Co., Ltd.) Specifically, the particle size of approximately 100,000 conductive particles was measured and the average value was calculated.

[0386] (6) Thickness of the conductive part

[0387] The obtained conductive particles were added to "TECHNOVIT4000" manufactured by Kulzer Co., Ltd. so as to have a content of 30% by weight and dispersed to prepare an embedding resin for inspection. An ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES Co., Ltd.) was used to cut out a cross section of the conductive particles dispersed in the embedding resin for inspection in a manner near the center.

[0388] Then, 10 conductive particles were randomly selected using a field emission transmission electron microscope (FE-TEM) (JEM-ARM200F manufactured by JEOL Ltd.), and the conductive portion of each conductive particle was observed. The thickness of the largest portion of the conductive portion in each conductive particle was measured, and the arithmetic average was taken as the thickness of the conductive portion.

[0389] (7) Agglomeration of Conductive Particles

[0390] The obtained conductive particles were observed to confirm whether aggregation of the conductive particles had occurred. Aggregation of the conductive particles was determined based on the following conditions.

[0391] [Criteria for Determining Aggregation of Conductive Particles]

[0392] ○○: No aggregation of conductive particles occurred

[0393] ○: A small amount of small aggregation occurred during the aggregation of conductive particles.

[0394] △: A small amount of conductive particles aggregated into large aggregates.

[0395] ×: Agglomeration of conductive particles occurred

[0396] Small aggregates refer to aggregates of four or less particles connected by a plating film, and large aggregates refer to aggregates of five or more particles connected by a plating film.

[0397] (8) Solder particle height

[0398] The obtained conductive particles were added to "TECHNOVIT4000" manufactured by Kulzer Co., Ltd. and dispersed in such a manner that the content of the conductive particles was 30% by weight, thereby preparing an embedding resin body for conductive particle inspection. An ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES Co., Ltd.) was used to cut out a cross section of the conductive particles so as to pass through the vicinity of the center of the conductive particles dispersed in the embedding resin body for inspection.

[0399] Then, conductive particles were randomly selected using a field emission scanning electron microscope (FE-SEM) to observe solder particles in the conductive particles. The heights of the solder particles at five locations in the conductive particles were measured, and the heights were arithmetic averaged to be the height of the solder particles.

[0400] (9) Aspect ratio of solder particles

[0401] The aspect ratio of the solder particle is the ratio of the height of the solder particle to the width of the solder particle (height of the solder particle / width of the solder particle), and is calculated from the height of the solder particle and the width of the solder particle.

[0402] The width of the solder particles is measured in the following manner.

[0403] The obtained conductive particles were added to "TECHNOVIT4000" manufactured by Kulzer Co., Ltd. and dispersed in such a manner that the content of the conductive particles was 30% by weight, thereby preparing a conductive particle inspection embedding resin body. An ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES Co., Ltd.) was used to cut out a cross section of the conductive particles so as to pass through the vicinity of the center of the conductive particles dispersed in the inspection embedding resin body.

[0404] Furthermore, a field emission scanning electron microscope (FE-SEM) was used to randomly select conductive particles and observe the solder particles in the conductive particles. The widths of the solder particles at 5 locations in the conductive particles were measured, and the arithmetic average was taken as the width of the solder particles. Based on the height of the obtained solder particles and the width of the solder particles, the aspect ratio of the solder particles (height of the solder particles / width of the solder particles) was calculated.

[0405] (10) The area of ​​the portion where the metal colloid precipitate or metal film exists out of 100% of the total surface area of ​​the solder particles (coverage rate of the metal colloid precipitate or metal film)

[0406] For the obtained conductive particles, the area of ​​the portion where the metal colloid precipitate or the metal film exists in 100% of the total surface area of ​​the solder particles (the coverage of the metal colloid precipitate or the metal film) is calculated. The coverage (coverage of the metal colloid precipitate or the metal film) can be calculated by performing SEM-EDX analysis on the cross section of the solder particles in the conductive particles and performing element mapping and image analysis.

[0407] The results are shown in Tables 1 to 4 below.

[0408]

[0409]

[0410]

[0411]

[0412] Explanation of symbols

[0413] 1…Conductive particles

[0414] 2…Base material particles

[0415] 3…Conductive part

[0416] 3A…1st conductive part

[0417] 3B…Second conductive part (solder part)

[0418] 11…Conductive particles

[0419] 12…Conductive part

[0420] 12A…1a conductive part

[0421] 12B…1b conductive part

[0422] 12C…Second conductive part (solder part)

[0423] 21…Conductive particles

[0424] 22…Conductive part

[0425] 22A…1st conductive part

[0426] 22B…Second conductive part (solder part)

[0427] 22Ba…Melted second conductive part (solder part)

[0428] 31…Conductive particles

[0429] 32…Conductive part

[0430] 32A…1st conductive part

[0431] 32B…Second conductive part (solder part)

[0432] 32C…3rd conductive part

[0433] 41…Conductive particles

[0434] 42…Conductive part

[0435] 42A…1st conductive part

[0436] 42B…Second conductive part (solder part)

[0437] 43…Metal colloid precipitate

[0438] 51…Conductive particles

[0439] 52…Conductive part

[0440] 52A…1a conductive part

[0441] 52B…1b conductive part

[0442] 52C…Second conductive part (solder part)

[0443] 53…Metal colloid precipitation

[0444] 61…Conductive particles

[0445] 62…Conductive part

[0446] 62A…1st conductive part

[0447] 62B…Second conductive part (solder part)

[0448] 63…metal film

[0449] 71…Conductive particles

[0450] 72…Conductive part

[0451] 72A…1a conductive part

[0452] 72B…1b conductive part

[0453] 72C…Second conductive part (solder part)

[0454] 73…metal film

[0455] 81…Connection structure

[0456] 82…First connection target component

[0457] 82a…1st electrode

[0458] 83…Second connection target component

[0459] 83a…Second electrode

Claims

1. A conductive particle comprising: Base material particles, and a conductive portion disposed on the surface of the substrate particle, The conductive part includes a component that can cause metal diffusion at a temperature below 400° C., or the conductive part can be melt-deformed at a temperature below 400° C., The conductive portion has a solder portion, The solder portion is a solder particle, The material of the solder particles is pure tin. The area of ​​the portion having the solder portion is 30% to 73% of the total surface area (100%) of the substrate particle.

2. The conductive particle according to claim 1, wherein The height of the solder particles is not less than 10 nm and not more than 10 μm.

3. The conductive particle according to claim 1 or 2, wherein The aspect ratio of the solder particles is 0.05 to 5.

4. The conductive particle according to claim 1 or 2, wherein The solder particles have metal colloid precipitates or metal films on their outer surfaces.

5. The conductive particle according to claim 4, wherein The area of ​​the portion having the metal colloid precipitate or the metal film is 5% or more and 100% or less of the total surface area of ​​the solder particle (100%). The conductive particle according to claim 4, wherein The metal type of the metal colloid precipitate or the metal type of the metal film is nickel, cobalt, lead, gold, zinc, palladium, copper, silver, bismuth or indium. 7 . The conductive particle according to claim 1 , wherein the particle diameter is 0.5 μm or more and 500 μm or less.

8. A conductive material comprising conductive particles and a binder, The said electroconductive particle is the electroconductive particle in any one of Claims 1-7.

9. A connection structure comprising: a first connection target member having a first electrode on a surface thereof, a second connection target member having a second electrode on a surface thereof, and a connecting portion connecting the first connection target member and the second connection target member, The connecting portion is formed of conductive particles, or is formed of a conductive material containing the conductive particles and a binder. The conductive particles are the conductive particles according to any one of claims 1 to 7, The first electrode and the second electrode are electrically connected via the conductive particles.

Citation Information

Patent Citations

  • Structure and method for connecting electronic component

    JP2000294997A

  • Metal atom-containing grain, connection material, connection structure, and method for producing connection structure

    JP2018046010A